Rechargeable battery with internal current limiter and internal current interrupter

By introducing a built-in current limiter and current interrupter into the lithium-ion battery, the resistive connection and gas generation of the cut-off current path is solved, and the thermal runaway problem of lithium-ion batteries is improved in the case of overcharge or overheating, and the safety and stability of the battery are improved.

JP2025020253AActive Publication Date: 2025-02-12AMERICAN LITHIUM ENERGY CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024190869
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2015-05-15
Filing Date
2024-10-30
Publication Date
2025-02-12
Estimated Expiration
2035-11-25

AI Technical Summary

Technical Problem

Existing high-energy density lithium-ion batteries are prone to thermal runaway when overcharged or overheated, resulting in combustion and explosion, and it is difficult to effectively control the internal current to prevent thermal runaway when internal short circuits are made.

Method used

Using a built-in current limiter and current interrupter, the internal current speed is limited by forming a resistive connection inside the battery, and a gas is generated when the temperature or voltage exceeds the limit, cutting off the current path to prevent thermal runaway.

Benefits of technology

It effectively reduces the risk of thermal runaway caused by internal short circuit, overcharging or overheating of lithium-ion batteries, and improves the safety and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020253000001_ABST
    Figure 2025020253000001_ABST
Patent Text Reader

Abstract

To provide a high energy density rechargeable (HEDR) battery capable of preventing the thermal runaway in the event of internal discharge or other disruption of a separator.SOLUTION: An improved high energy density rechargeable battery comprises: a first electrode; a first current collector for transferring electrons; a current interrupter 8 interposed between the first electrode and the first current collector, where the current interrupter 8 comprises a heat sensitive material configured to generate a gas upon activation by at least a temperature trigger, where the generation of the gas forms a nonconductive gap between the first electrode and the first current collector, and where the formation of the nonconductive gap electrically decouples the first electrode from the first current collector; a second electrode having a polarity opposite to that of the first electrode; and a separator 2 interposed between the first electrode and the second electrode. Preferably, the battery further comprises a current limiter.SELECTED DRAWING: Figure 6D
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. application Ser. No. 14 / 714,160, filed May 15, 2015, and entitled "Rechargeable Battery With Internal Current Limiter and Internal Current Interrupter," as well as the following five provisional applications: U.S. Provisional Application No. 62 / 084,454, filed November 25, 2014, and entitled "Battery Safety Apparatus;" U.S. Provisional Application No. 62 / 084,454, filed February 9, 2015, and entitled "Rechargeable Battery With Resistive Layer for Improved Safety;" No. 62 / 114,001, U.S. Provisional Application No. 62 / 114,006, filed February 9, 2015, and entitled "Rechargeable Battery With Temperature Activated Current Interrupter," U.S. Provisional Application No. 62 / 114,007, filed February 9, 2015, and entitled "Voltage Current Interrupter," and U.S. Provisional Application No. 62 / 114,508, filed February 10, 2015, and entitled "Rechargeable Battery With Internal Current Limiter and Internal Current Interrupter," the entire disclosures of which are incorporated herein by reference.

[0002] This disclosure relates to an internal current limiter or interrupter used to protect batteries from thermal runaway caused by internal short circuits or overcharging, particularly for high energy density rechargeable (HEDR) batteries with improved safety. [Background technology]

[0003] There is a need for safe rechargeable battery systems that have high energy density and are thereby capable of storing and delivering large amounts of electrical energy per unit volume and / or weight. Such stable, high energy battery systems have important utility in many applications, including military equipment, communications equipment, and robotics.

[0004] One example of a commonly used high energy density rechargeable (HEDR) battery is the lithium ion battery. Summary of the Invention [Problem to be solved by the invention]

[0005] Lithium-ion batteries are rechargeable batteries in which lithium ions move from the negative electrode to the positive electrode during discharge and vice versa during charging. Lithium-ion batteries can be dangerous and pose a safety hazard under certain conditions. The fire energy content (electrical + chemical) of a lithium cobalt oxide battery is about 100-150 kJ per ampere-hour, most of which is chemical. When overcharged or overheated, lithium-ion batteries can suffer thermal runaway and cell rupture. In extreme cases, this can cause combustion. Also, an external or internal short circuit in the battery can cause the battery to overheat and catch fire.

[0006] overcharging In a lithium-ion battery, useful work is performed when electrons flow through a closed external circuit. However, to maintain charge neutrality, for each electron that flows through the external circuit, there must be a corresponding lithium ion that moves from one electrode to the other. The electrical potential that facilitates this movement is achieved by oxidizing transition metals. For example, cobalt (Co) becomes Co when charging. 3+ From Co 4+ During discharge, it changes to Co 4+ From Co 3+ Conventionally, Li 1-x CoO2 is used, where the coefficient x is the ratio of the lithium ion to the oxidation state of CoO2, i.e., Co 3+ Or Co 4+ Using these conventions, the positive electrode half reaction of a lithium cobalt battery can be expressed as: TIFF2025020253000082.tif7150The negative electrode half reaction is expressed as follows: TIFF2025020253000083.tif7150The cobalt electrode reaction is reversible if limited to x<0.5 and to an acceptable depth of discharge due to cycle life issues and stability of LiCoO2. Overcharging leads to the formation of cobalt(IV) oxide as follows: TIFF2025020253000084.tif5150LiCoO2 decomposes to CoO2, releasing large amounts of heat and oxygen. The released oxygen oxidizes the electrolyte, which leads to thermal runaway. This process is irreversible. Therefore, a device or structure that can decompose below or before the actual decomposition is needed. This device can protect the cell from thermal expansion.

[0007] thermal runaway When the heat generated by a lithium-ion battery exceeds its heat dissipation capabilities, the battery becomes susceptible to thermal runaway, which can lead to overheating and destructive consequences such as fire or explosion. Thermal runaway is a positive feedback loop that changes the system such that an increase in temperature leads to an even higher temperature. The excessive heat can be due to battery mishandling, battery failure, accidents, or other causes. However, excessive heat is often due to increased Joule heating caused by excessive internal current or exothermic reactions between the positive and negative electrodes. There are various causes for excessive internal current, but one contributing factor may be a short circuit of the separator, such as conductive particles penetrating the separator, lowering the internal resistance. The heat caused by the short circuit of the separator can cause further damage in the separator, leading to mixing of the negative and positive electrode reagents and the resulting generation of more heat due to exothermic reactions.

[0008] Internal Short Circuit Lithium-ion batteries use a separator between the positive and negative electrodes to electrically separate the two electrodes from each other while allowing lithium ions to pass through. When the battery performs work by passing electrons through an external circuit, the lithium-ion permeability of the separator allows the battery to close the circuit. Short circuits across the separator can result from improper charging and discharging, or defects in battery manufacturing such as metal impurities and metal debris formation during electrode manufacturing. More specifically, improper charging precipitates metallic lithium dendrites on the surface of the negative electrode, and these dendrites grow and penetrate the separator to provide a conductive path for electrons from one electrode to the other. In addition, improper discharge below 1.5V can cause copper dissolution, eventually resulting in the formation of metallic copper dendrites on the surface of the negative electrode, which can also grow through the separator through nanopores. The low resistance of these conductive paths results in rapid discharge and large Joule heat generation, which can cause overheating and thermal runaway.

[0009] To avoid fire and / or explosion, what was needed was a combination of an internal current limiter and an internal current interrupter that could first limit the internal discharge caused by an internal short circuit to reduce the generation of Joule heat if the rate of the internal discharge was insufficiently limited, and also interrupt the internal short circuit to further suppress the rate of the internal discharge regardless of the temperature rise. [Means for solving the problem]

[0010] In a first aspect, an improved high energy density rechargeable (HEDR) battery is provided, as described in some embodiments herein, which includes two electrodes of opposite polarity, each electrode characterized by a resistance, a safe operating temperature range, and a safe charging voltage, and a separator that separates the two electrodes and prevents internal discharge between them. The HEDR battery includes at least one electrode that uses a current collector to transfer electrons, and the separator is at risk of creating a short circuit, which potentially allows a short circuit between the two electrodes, and the rapid internal discharge between the two electrodes thereby allowing rapid generation of Joule heat, which potentially allows thermal runaway. In the HEDR battery, the two electrodes are at risk of overcharging beyond a safe charging voltage, which would create a short circuit, and the two electrodes may be at risk of thermal runaway beyond a safe operating temperature range. The HEDR battery may include improvements for slowing the rate of internal discharge due to short circuits, slowing the generation of Joule heat therefrom, and reducing the risk of thermal runaway, including a current limiter forming an electrical connection between one of the electrodes and its corresponding current collector, the current limiter having a resistivity for resistively blocking current passing therethrough and for diverting current away from the electrode current collector to which it is connected if the separator forms a short circuit, and for reducing the rate of internal discharge between the two electrodes, and a current interrupter having an engaged configuration, a disengaged configuration, and a gas generation element for switching the current interrupter from the engaged configuration to the disengaged configuration. The gas generation element may have a trigger for generating gas, the trigger being selected from the group consisting of a temperature trigger and a voltage trigger, the temperature trigger may be operable above a safe operating temperature range. A voltage trigger is operable above a safe charging voltage to electrically couple the current interrupter between one of the electrodes and its corresponding current collector using a laminate connection in an engaged configuration, and in a disengaged configuration, the laminate connection is peeled away and the current interrupter forms a non-conductive gap that breaks the electrical coupling between the electrode and its corresponding current collector.The current interrupter initiates operation of the gas generating element in response to a trigger to transition from an engaged configuration to a disengaged configuration, and the generated gas delaminates the laminate structure to interrupt the electrical connection between the electrode and its corresponding current collector. The combined use of the current limiter and current interrupter reduces the risk of shorting the separator, overcharging the electrodes, and thermal runaway due to overheating the electrodes.

[0011] The following features may be present in an improved high energy density rechargeable (HEDR) battery in any suitable combination: the current limiter and the current interrupter may be simultaneously incorporated by lamination into a protective layer interposed between the same electrode and current collector; the HEDR battery may include two current collectors including a first current collector and a second current collector, and two electrodes including a first electrode and a second electrode, the first electrode including a first portion and a second portion, the second portion of the first electrode being interposed between the first portion of the first electrode and the first current collector, the improvement being further characterized as follows: the current limiter is laminated between the first portion of the first electrode and the second portion of the first electrode, and the current interrupter is laminated between the second portion of the first electrode and the first current collector. The current limiter can be laminated between the second portion of the first electrode and the first current collector, and the current interrupter can be laminated between the first portion of the first electrode and the second portion of the first electrode. The HEDR battery can include two current collectors including a first current collector and a second current collector, and two electrodes including a first electrode and a second electrode, and the current limiter can be laminated between the first electrode and the first current collector, and the current interrupter can be laminated between the second electrode and the second current collector. In the HEDR battery, each electrode can have a temperature range for safe operation and an internal resistivity, and the current limiter can have a resistivity within the temperature range for safe operation that is greater than the internal resistivity of the electrode with which it is laminated. The current limiter can lack a resistivity transition switch at a temperature within the temperature range for safe operation. The HEDR battery can have each electrode having a temperature range for standard operation, and the current limiter can have a resistivity transition that is less than the internal resistivity of the electrode at the temperature range for standard operation and is greater than the internal resistivity of the electrode above the temperature range for standard operation.The HEDR battery can have each electrode having a temperature range for standard operation, and the current interrupter can be operable at temperatures above the temperature range for standard operation.In some embodiments, the HEDR battery may be of a type where each electrode has a temperature range for standard operation and a temperature range for safe operation, and the current interrupter operates at a temperature above the temperature range for standard operation and within the temperature range for safe operation. In some embodiments, the HEDR battery may be of a type where each battery has an internal resistance within the temperature range for safe operation, and the current limiter has a resistivity within the temperature range for safe operation that is greater than the internal resistivity of the electrode with which it is laminated. The current limiter and the current interrupter may be incorporated together by lamination into a protective layer interposed between the same electrode and current collector. The HEDR battery may be of a type where each electrode has a voltage range for standard operation and the current interrupter is activated at a voltage above the voltage range for standard operation. The HEDR battery may be of a type where each battery has a voltage range for standard operation and a voltage range for safe operation, and the current interrupter is activated at a voltage above the voltage range for standard operation and within the voltage range for safe operation. The current limiter and the current interrupter can be simultaneously incorporated by lamination into a protective layer interposed between the same electrode and current collector.

[0012] In a related aspect, there is provided an improved high energy density rechargeable (HEDR) battery as described herein, the rechargeable battery comprising two electrodes of opposite polarity, a separator separating the two electrodes, and at least one current collector electrically coupled to one of the two electrodes, the separator preventing internal discharge between the two electrodes, whereby damage to the separator could potentially result in internal discharge between the two electrodes, whereby the internal discharge could result in the generation of Joule heat as a potential hazard, and the rechargeable battery comprising a thermally actuated current interrupter and a voltage actuated current interrupter. A thermally actuated current interrupter can be laminated between one of the current collectors and one of the electrodes by a lamination method, the thermally actuated current interrupter electrically connecting the current collector to the electrode with which it is laminated when deactivated, and peeling off from the current collector when activated to form a non-conductive gap to electrically isolate the current collector from the electrode with which it is laminated when it is activated, the electrical isolation slowing down the rate of internal discharge between the two electrodes in the event of separator damage. A voltage-actuated current interrupter can be laminated between one of the current collectors and one of the electrodes by a lamination method, the voltage-actuated current interrupter electrically connecting the current collector to the electrode with which it is laminated when it is deactivated, and peeling off from the current collector when activated to form a non-conductive gap to electrically isolate the current collector from the electrode with which it is laminated when it is activated, the electrical isolation slowing down the rate of internal discharge between the two electrodes in the event of separator damage. In HEDR batteries, in the event of separator failure, activation of either a thermally activated current interrupter or a voltage activated current interrupter can slow the generation of Joule heat to reduce potential hazards.

[0013] In a further related aspect, in some embodiments described herein, there is provided a method of avoiding internal thermal runaway in a high energy density rechargeable battery in which separator failure leads to internal discharge, the method comprising delaminating an electrode in the battery from a current collector by generating gas from a thermally sensitive gas-generating material in a barrier layer interposed between the electrode and the current collector, the delamination electrically isolating the electrode from the current collector and slowing the rate of internal discharge.

[0014] In a first aspect, there is provided herein an improved high energy density rechargeable (HEDR) battery, the rechargeable battery including an anode energy layer, a cathode energy layer, a separator disposed between the anode energy layer and the cathode energy layer to prevent internal discharge, at least one current collector in electronic communication with either the anode energy layer or the cathode energy layer, and a resistive layer interposed between the separator and one of the current collectors, the anode energy layer and the cathode energy layer each having an internal resistivity, the HEDR battery having a preferred temperature range for discharging a current and an upper temperature safety limit. and an upper temperature safety limit, wherein the resistive layer is configured to limit the rate of internal discharge through the separator in the event of separator failure and the resulting generation of Joule heating, the resistive layer having a constant resistivity at temperatures between a preferred temperature range and an upper temperature safety limit, the constant resistivity of the resistive layer being greater than the internal resistivity of either energy layer, and the resistive layer is for avoiding temperatures exceeding the upper temperature safety limit in the event of separator failure.

[0015] The following features, in suitable combination, may be included in a HEDR battery: In some embodiments, the resistive layer of a HEDR battery may be porous and include a ceramic powder defining a void space, a binder partially filling the void space to bind the ceramic powder, and a conductive component dispersed within the binder and imparting resistivity to the resistive layer, the void space being partially unfilled to impart porosity and permeability to the resistive layer. The resistive layer may be compressed to reduce the unfilled void space and increase the binding of the ceramic powder by the binder. The resistive layer may include greater than 30% by weight of the ceramic powder. The resistive layer may include greater than 50% by weight of the ceramic powder. The resistive layer may include greater than 70% by weight of the ceramic powder. The resistive layer may include greater than 75% by weight of the ceramic powder. The resistive layer may include greater than 80% by weight of the ceramic powder. The resistive layer of a HEDR battery may be permeable to the movement of ionic charge carriers. The resistive layer may be porous and may comprise a composition including a non-conductive filler, a binder binding the non-conductive filler, and a conductive component dispersed in the binder that imparts resistivity to the resistive layer. The resistive layer may be impermeable to movement of ionic charge carriers. The constant resistivity of the resistive layer of the HEDR cell may be at least two times the internal resistivity of either of the energy layers. The constant resistivity of the resistive layer of the HEDR cell may be at least five times the internal resistivity of either of the energy layers. The constant resistivity of the resistive layer of the HEDR cell may be at least ten times the internal resistivity of either of the energy layers. The resistive layer may be free of a solid-phase to non-solid-phase transformation to convert the resistivity of the resistive layer from a low resistivity to a high resistivity at a temperature between the maximum operating temperature and an upper temperature safety limit. The resistive layer may be non-sacrificial at a temperature below an upper temperature safety limit. The resistive layer may be sacrificial at a temperature above an upper temperature safety limit. The resistive layer may comprise a ceramic powder that chemically decomposes at a temperature above an upper temperature safety limit to generate a flammable gas. The resistive layer may include a ceramic powder that chemically decomposes above an upper temperature safety limit to generate gases that cause the current collector to peel off from the resistive layer.The current collector can include an anode current collector for electronic communication with the anode energy layer, and the resistive layer is interposed between the separator and the anode current collector. The resistive layer can be interposed between the anode current collector and the anode energy layer. The resistive layer can be interposed between the anode energy layer and the separator. In some embodiments, the anode energy layer of the HEDR cell includes a first anode energy layer and a second anode energy layer interposed between the first anode energy layer and the separator, and the resistive layer is interposed between the first anode energy layer and the second anode energy layer. The current collector can include a cathode current collector for electronic communication with the cathode energy layer, and the resistive layer is interposed between the separator and the cathode current collector. The resistive layer can be interposed between the cathode current collector and the cathode energy layer. The resistive layer can be interposed between the cathode energy layer and the separator. The cathode energy layer can include a first cathode energy layer and a second cathode energy layer interposed between the first cathode energy layer and a separator, and the resistive layer is interposed between the first cathode energy layer and the second cathode energy layer. In some embodiments, the HEDR cell can include two current collectors, the two current collectors including an anode current collector in electronic communication with the anode energy layer and a cathode current collector in electronic communication with the cathode energy layer, and the resistive layer includes an anode resistive layer and a cathode resistive layer, the anode resistive layer being interposed between the separator and the anode current collector, and the cathode resistive layer being interposed between the separator and the cathode current collector.

[0016] In a related aspect, there is provided a method of limiting a rate of internal discharge of an energy layer due to separator failure within a high energy density rechargeable (HEDR) battery as described herein, the method comprising resisting internal discharge with a resistive layer, the resistive layer being interposed between a separator and a current collector in the HEDR battery, the resistive layer having a constant resistivity at a temperature between a preferred temperature range for discharging the energy layer and an upper temperature safety limit, the constant resistivity of the resistive layer being greater than the internal resistivity of the energy layer.

[0017] In some embodiments described herein, a high energy density rechargeable (HEDR) metal ion battery is provided, the battery including an anode energy layer, a cathode energy layer, a separator separating the anode energy layer from the cathode energy layer, at least one current collector in electronic communication with either the anode energy layer or the cathode energy layer, and a barrier layer operable to interrupt electrical current within the high energy density rechargeable metal ion battery upon exposure to a temperature at or above an upper temperature safety limit, the high energy density rechargeable metal ion battery having an upper temperature safety limit to avoid thermal runaway, the barrier layer being interposed between the separator and one of the current collectors, the barrier layer comprising: When not in operation, the blocking layer is laminated between the separator and one of the current collectors to allow current to flow, while when in operation, the blocking layer is peeled off to interrupt the current flowing through the high energy density rechargeable metal ion battery, the blocking layer including a temperature-sensitive decomposable component that decomposes when exposed to a temperature at or above an upper temperature safety limit, the temperature-sensitive decomposable component generating a gas upon decomposition, and the generated gas peels off the blocking layer to interrupt the current flowing through the high energy density rechargeable metal ion battery, and the high energy density rechargeable metal ion battery avoids thermal runaway by activating the blocking layer by exposing the battery to a temperature at or above an upper temperature safety limit to interrupt the current in the high energy density rechargeable metal ion battery.

[0018] The following features, in suitable combination, may be present in a HEDR metal ion battery: The barrier layer may be porous. The temperature sensitive decomposable component may include a ceramic powder. The barrier layer may include a composition including a ceramic powder, a binder, and a conductive component. The ceramic powder may define a void space. The binder may partially fill the void space to bind the ceramic powder. The conductive component may be dispersed within the binder to impart electrical conductivity to the barrier layer. The void space is partially unfilled to impart porosity and permeability to the barrier layer. The barrier layer may include greater than 30% by weight ceramic powder. The barrier layer may include greater than 50% by weight ceramic powder. The barrier layer may include greater than 70% by weight ceramic powder. The barrier layer may include greater than 75% by weight ceramic powder. The barrier layer may include greater than 80% by weight ceramic powder. The barrier layer may be permeable to the movement of ionic charge carriers. The barrier layer may be porous and may comprise a composition including a non-conductive filler, a binder binding the non-conductive filler, and a conductive component dispersed in the binder that imparts resistivity to the barrier layer. The barrier layer may be impermeable to movement of ionic charge carriers. The barrier layer may be sacrificial at temperatures above an upper temperature safety limit. The barrier layer may comprise a ceramic powder that chemically decomposes at temperatures above an upper temperature safety limit to generate a flammable gas. The current collector may comprise an anode current collector for electronic communication with the anode energy layer, and the barrier layer is interposed between the separator and the anode current collector. The barrier layer may be interposed between the anode current collector and the anode energy layer. The barrier layer may be interposed between the anode energy layer and the separator. The anode energy layer of the HEDR battery includes a first anode energy layer and a second anode energy layer interposed between the first anode energy layer and a separator, and a barrier layer is interposed between the first anode energy layer and the second anode energy layer.The current collector can include a cathode current collector for communicating electrons with the cathode energy layer, with the barrier layer being interposed between the separator and the cathode current collector. The barrier layer can be interposed between the cathode current collector and the cathode energy layer. The barrier layer can be interposed between the cathode energy layer and the separator. The cathode energy layer can include a first cathode energy layer and a second cathode energy layer interposed between the first cathode energy layer and the separator, with the barrier layer being interposed between the first cathode energy layer and the second cathode energy layer. The HEDR battery can further include two current collectors, including an anode current collector in electronic communication with the anode energy layer and a cathode current collector in electronic communication with the cathode energy layer, and the blocking layer includes an anode blocking layer and a cathode blocking layer, the anode blocking layer being sandwiched between the separator and the anode current collector, and the cathode blocking layer being sandwiched between the separator and the cathode current collector.

[0019] In a related aspect, a method is provided for interrupting electrical current flow through a high energy density rechargeable metal ion battery upon exposure to a temperature at or above an upper temperature safety limit to avoid thermal runaway, the method comprising raising the temperature of the high energy density rechargeable metal ion battery above the upper temperature safety limit and activating a barrier layer that interrupts electrical current flow through the high energy density rechargeable metal ion battery. The high energy density rechargeable metal ion battery includes an anode energy layer, a cathode energy layer, a separator separating the anode energy layer from the cathode energy layer, a current collector exchanging electrons with either the cathode energy layer or the anode energy layer, and a barrier layer, the barrier layer being interposed between the separator and one of the current collectors, the barrier layer being laminated between the separator and one of the current collectors to allow current to flow when the battery is not in operation, and being peeled off to interrupt current flow through the lithium ion battery when the battery is in operation, the barrier layer including a temperature-sensitive decomposable component that decomposes when exposed to a temperature at or above an upper temperature safety limit, the temperature-sensitive decomposable component generating gas when decomposed, and the generated gas peeling off the barrier layer to interrupt current flow through the high energy density rechargeable metal ion battery, thereby preventing thermal runaway of the high energy density rechargeable metal ion battery by interrupting current flow through the battery.

[0020] In some embodiments herein, a high energy density rechargeable (HEDR) metal-ion battery is provided, the battery including an anode energy layer, a cathode energy layer, a separator separating the anode energy layer from the cathode energy layer, an anode current collector in electronic communication with the anode energy layer, and a barrier layer operable to interrupt current flow in the high energy density rechargeable metal-ion battery upon exposure to a voltage exceeding a maximum safe voltage, the high energy density rechargeable metal-ion battery being rechargeable and characterized by a maximum safe voltage to avoid overcharging, the barrier layer being operable to interrupt current flow in the cathode energy layer, the barrier layer being operable to interrupt current flow in the cathode energy layer, the barrier layer being operable to interrupt current flow in the cathode energy layer, the barrier layer being operable to interrupt current flow in the anode .... The blocking layer is sandwiched between the anode energy layer and the cathode current collector, and when not in operation, the blocking layer is laminated on the anode current collector to conduct electricity, and when in operation, the blocking layer is peeled off from the anode current collector to block current. The blocking layer includes a voltage-sensitive decomposable component that decomposes when exposed to a voltage exceeding a maximum safe voltage, and the voltage-sensitive decomposable component generates gas upon decomposition, and the generated gas peels off the blocking layer from the anode current collector to block current. Thus, when the high energy density rechargeable metal ion battery is exposed to a voltage exceeding a maximum safe voltage, the blocking layer is activated to block current, thereby avoiding overcharging.

[0021] The following features, in suitable combination, may be present in a high energy density rechargeable metal ion battery: The barrier layer of a HEDR battery may be porous and may also include a composition including a ceramic powder defining a void space, a binder partially filling the void space to bind the ceramic powder, and a conductive component dispersed within the binder to impart electrical conductivity to the barrier layer, the void space being partially unfilled to impart porosity and permeability to the barrier layer. The barrier layer may be compressed to reduce the unfilled void space and increase the bonding of the ceramic powder by the binder. The barrier layer may include greater than 30% by weight ceramic powder. The barrier layer may include greater than 50% by weight ceramic powder. The barrier layer may include greater than 70% by weight ceramic powder. The barrier layer may include greater than 75% by weight ceramic powder. The barrier layer may include greater than 80% by weight ceramic powder. The barrier layer may be permeable to the movement of ionic charge carriers. The barrier layer of a HEDR battery may be porous and may comprise a composition including a non-conductive filler, a binder that binds the non-conductive filler, and a conductive component dispersed in the binder that imparts resistivity to the barrier layer. The barrier layer may be impermeable to movement of ionic charge carriers. The barrier layer may be sacrificial at voltages above the maximum safe voltage for recharging. The barrier layer may comprise a ceramic powder that chemically decomposes at voltages above the maximum safe voltage to generate a gas. The gas may be a non-flammable gas.

[0022] In a related aspect, a method is provided for shutting down the recharge process of a high energy density rechargeable metal ion battery upon exposure to a voltage at or above a maximum safe voltage to avoid overcharging, the high energy density rechargeable metal ion battery including an anode energy layer, a cathode energy layer, a separator separating the anode energy layer from the cathode energy layer, and an anode current collector in electronic communication with the anode energy layer, the method including overcharging the high energy density rechargeable metal ion battery to increase the voltage above a maximum safe voltage for recharging, and shutting down the overcharge by generating gas through decomposition of a voltage sensitive decomposable component in a barrier layer laminated to the anode current collector, the generated gas causing the barrier layer to delaminate from the anode current collector, whereby overcharging of the high energy density rechargeable metal ion battery is shut down by the delamination of the barrier layer from the anode current collector due to gas generation in the barrier layer.

[0023] One embodiment of the present disclosure relates to an improved high energy density rechargeable (HEDR) battery, which is of the type including two electrodes (12 and 14) of opposite polarity. Each electrode is characterized by its resistivity, its safe operating temperature range, and its safe charging voltage. The HEDR is of the type including at least one electrode (12 or 14) using a separator 2 that separates the two electrodes (12 and 14) and prevents internal discharge between the two electrodes, and a current collector 4 for transferring electrons. The separator 2 is at risk of forming a short circuit. A short circuit can result in a rapid internal discharge between the two electrodes (12 and 14), which can result in a rapid generation of Joule heat, which can result in thermal runaway. The two electrodes (12 and 14) are at risk of overcharging beyond a safe charging voltage and the resulting formation of a short circuit. The two electrodes (12 and 14) are at risk of thermal runaway at temperatures above a safe operating temperature range.

[0024] Improvements to the first aspect of the present disclosure can be used to slow the rate of internal discharge due to a short circuit, slow the resulting generation of Joule heat, and reduce the risk of thermal runaway.

[0025] The improvement involves adding a current limiter 6 in combination with a current interrupter 8 to the HEDR battery.

[0026] The current limiter 6 forms an electrical connection between one of the electrodes (12 or 14) and its corresponding current collector 4. The current limiter 6 has a resistivity that resistively blocks current and diverts current away from the associated electrode current collector 4 if the separator 2 forms a short circuit, and reduces the rate of internal discharge between the two electrodes (12 and 14).

[0027] The current interrupter 8 has an engaged configuration, a disengaged configuration, and a gas generating element for transitioning the current interrupter 8 from the engaged configuration to the disengaged configuration. The gas generating element has a trigger for generating gas. The trigger is selected from the group consisting of a temperature trigger and a voltage trigger.

[0028] The temperature trigger operates at temperatures above the safe operating temperature range.

[0029] The voltage trigger operates at voltages above the safe charging voltage.

[0030] In the engaged configuration, the current interrupter 8 electrically couples one of the electrodes (12 or 14) to its corresponding current collector 4 through a laminated connection.

[0031] In the disengaged configuration, the lamination connection peels away and the current interrupter 8 creates a non-conductive gap to break the electrical coupling between the electrode ( 12 or 14 ) and its corresponding current collector 4 .

[0032] The current interrupter 8 transitions from the engaged to the disengaged configuration by initiating operation of the gas generating element in response to a trigger. The generated gas peels off the lamination connection to interrupt the electrical coupling between the electrode (12 or 14) and its corresponding current collector 4.

[0033] In a first aspect of the present disclosure, the current limiter 6 and current interrupter 8 are configured in combination to reduce the risk of thermal runaway due to shorting of the separator, overcharging of the electrodes, and overheating of the electrodes.

[0034] In one embodiment of the first aspect of the present disclosure, the current limiter 6 and the current interrupter 8 are simultaneously incorporated into the protective layer by being interposed between the same electrode (12 or 14) and the current collector 4 by lamination.

[0035] In another embodiment of the first aspect of the present disclosure, the battery is of the type including two current collectors 4 including a first current collector 4 and a second current collector 4. The two electrodes (12 and 14) include a first electrode and a second electrode. The first electrode includes a first portion and a second portion. The second portion of the first electrode is interposed between the first portion of the first electrode and the first current collector 4. A further feature of the improvement of this embodiment of the present disclosure is that a current limiter 6 is laminated between the first portion of the first electrode and the second portion of the first electrode, and a current interrupter 8 is laminated between the second portion of the first electrode and the first current collector 4. In a sub-embodiment of the first aspect of the present disclosure, the current limiter 6 is laminated between the second portion of the first electrode and the first current collector 4, and the current interrupter 8 is laminated between the first portion of the first electrode and the second portion of the first electrode.

[0036] In another embodiment of the first aspect of the present disclosure, the battery is of the type including two current collectors 4 including a first current collector 4 and a second current collector 4, and two electrodes (12 and 14) including a first electrode and a second electrode, the improvement having further features. In this embodiment, a current limiter 6 is laminated between the first electrode and the first current collector 4, and a current interrupter 8 is laminated between the second electrode and the second current collector 4.

[0037] In another embodiment of the first aspect of the present disclosure, the battery is of a type in which each electrode (12 or 14) has a temperature range and internal resistivity for safe operation. In this embodiment, the current limiter 6 has a resistivity greater than the internal resistivity of the electrode (12 or 14) with which it is stacked, within the temperature range for safe operation.

[0038] In another embodiment of the first aspect of the present disclosure, a further feature of the improvement is that the current limiter 6 is devoid of a resistivity transition switch at temperatures within the temperature range for safe operation.

[0039] In another embodiment of the first aspect of the disclosure, the battery is of a type in which each electrode (12 and 14) has a temperature range for standard operation. In this embodiment, the current limiter 6 effects a resistivity transition at a resistivity lower than the internal resistivity of the electrode (12 and / or 14) within the temperature range for standard operation, and at a resistivity higher than the internal resistivity of the electrode (12 and / or 14) at temperatures above the temperature range for standard operation.

[0040] In another embodiment of the first aspect of the present disclosure, the battery is of a type in which each electrode (12 and 14) has a temperature range for standard operation. In this embodiment, the current interrupter 8 operates at a temperature that exceeds the temperature range for standard operation.

[0041] In another embodiment of the first aspect of the present disclosure, the battery is of a type in which each electrode (12 and 14) has a temperature range for normal operation and a temperature range for safe operation. In this embodiment, the current interrupter 8 operates at a temperature above the temperature range for normal operation and within the temperature range for safe operation.

[0042] In another embodiment of the first aspect of the disclosure, the battery has each cell (12 and 14) having an internal resistivity within a temperature range for safe operation. In this embodiment, the current limiter 6 has a resistivity within a temperature range for safe operation that is higher than the internal resistivity of the electrode (12 or 14) with which it is laminated. As an alternative to this embodiment, the current limiter 6 and the current interrupter 8 are incorporated together in a protective layer laminated between the same electrode (12 or 14) and the current collector 4.

[0043] In another embodiment of the first aspect of the present disclosure, the battery is of a type in which each electrode (12 and 14) has a voltage range for standard operation. In this embodiment, the current interrupter 8 operates at a voltage that exceeds the voltage range for standard operation.

[0044] In another embodiment of the first aspect of the present disclosure, the battery has each electrode (12 and 14) having a voltage range for normal operation and a voltage range for safe operation. In this embodiment, the current interrupter 8 operates at a voltage above the voltage range for normal operation and within the voltage range for safe operation. As an alternative to this embodiment, the current limiter 6 and the current interrupter 8 are incorporated together in a protective layer interposed by lamination between the same electrode (12 or 14) and the current collector 4.

[0045] A second aspect of the present disclosure is another improved high energy density rechargeable battery, the battery being of a type having two electrodes (12 and 14) of opposite polarity, a separator 2 separating the two electrodes (12 and 14), and at least one current collector 4 electrically coupling one of the electrodes (12 or 14). The separator 2 prevents internal discharge between the two electrodes (12 and 14). Breakage of the separator 2 may result in internal discharge between the two electrodes (12 and 14). The internal discharge results in the generation of Joule heat as a potential hazard.

[0046] The improvement of the second aspect of the present disclosure includes a thermally activated current interrupter 8 and a voltage activated current interrupter 8 .

[0047] The thermally actuated current interrupter 8 is laminated between one of the current collectors 4 and one of the electrodes (12 or 14) by a lamination technique. When unactivated, the thermally actuated current interrupter 8 electrically couples the current collector 4 to the electrode (12 or 14) with which it is laminated. When activated, the thermally actuated current interrupter 8 peels away from the current collector 4 to form a non-conductive gap that electrically isolates the current collector 4 from the electrode (12 or 14) with which it was laminated. The electrical isolation slows down the rate of internal discharge between the two electrodes (12 and 14) in the event of separator failure.

[0048] The voltage-activated current interrupter 8 is laminated between one of the current collectors 4 and one of the electrodes (12 or 14) by lamination. When unactivated, the voltage-activated current interrupter 8 electrically couples the current collector 4 to the electrode (12 or 14) with which it is laminated. When activated, the voltage-activated current interrupter 8 peels off from the current collector 4 to form a non-conductive gap that electrically isolates the current collector 4 from the electrode (12 or 14) with which it was laminated. The electrical isolation slows down the rate of internal discharge between the two electrodes (12 and 14) in the event of separator failure. In the second aspect of the present disclosure, in the event of separator failure, either the heat-activated current interrupter 8 or the voltage-activated current interrupter 8 can be activated to slow down the generation of Joule heat and reduce potential hazards.

[0049] A second aspect of the present disclosure relates to a method for avoiding thermal runaway in a high energy density rechargeable battery that suffers from internal discharge due to separator failure. The method includes the step of peeling an electrode (12 or 14) in the battery from a current collector 4 by generating gas from a thermally sensitive gas generating material in a barrier layer interposed between the electrode (12 or 14) and the current collector 4. The peeling electrically isolates the electrode (12 or 14) from the current collector to slow the rate of internal discharge.

[0050] A third aspect of the present disclosure relates to a method for avoiding thermal runaway in a high energy density rechargeable battery that may suffer separator damage due to voltage overcharge. The method includes peeling an electrode (12 or 14) in the battery from a current collector 4 by generating gas from a thermally sensitive gas generating material in a barrier layer interposed between the electrode (12 or 14) and a current collector 4. The peeling electrically isolates the electrode (12 or 14) from the current collector to interrupt voltage overcharge.

[0051] A fourth aspect of the present disclosure relates to a method for avoiding thermal runaway in high energy density rechargeable batteries that may suffer separator damage due to voltage overcharge. The method includes the step of peeling an electrode (12 or 14) in the battery from a current collector 4 by generating gas from a voltage-sensitive or temperature-sensitive material that indirectly forms gas via decomposition compounds (at high voltages) that react with battery elements such as the electrolyte and electrode (12 or 14). The voltage-sensitive or temperature-sensitive material, also called a gas generating agent, can be included in a barrier layer interposed between the electrode (12 or 14) and the current collector 4. The peeling electrically isolates the electrode (12 or 14) from the current collector to interrupt voltage overcharge.

[0052] The present disclosure will now be described in more detail with reference to the accompanying drawings, in which several exemplary embodiments of the present disclosure are shown. As will be understood by those skilled in the art, the described embodiments can be modified in various different ways without departing from the spirit or scope of the present disclosure. Thus, the drawings and descriptions should be regarded as illustrative in nature, and not restrictive. In the drawings, thicknesses of layers and regions are exaggerated for clarity. [Brief description of the drawings]

[0053] [Figure 1] 1A-1G are schematic diagrams illustrating exemplary configurations of a film-type lithium ion battery having one or more resistive layers that function as a current limiter 6 to protect the battery from overheating in the event of an internal short circuit, and in combination with a thermally activated current interrupter 8 upon increasing temperature, to irreversibly interrupt the self-discharge process if the battery overheats or reaches a dangerous temperature. [Diagram 2]2A-2B are schematic diagrams illustrating an exemplary configuration of a film-type lithium ion battery having one or more layers that function as a combination of a current limiter 6 and a current interrupter 8 to protect the battery from overheating in the event of an internal short circuit, and in combination with a current interrupter 8 that can be voltaically activated by an increase in voltage to irreversibly interrupt the self-discharge process if the battery is overcharged. [Diagram 3] 3A and 3B are schematic diagrams illustrating exemplary configurations of a film-type lithium ion battery having one or more resistive layers functioning as a current limiter 6 to protect the battery from overheating in the event of an internal short circuit, in combination with a current interrupter 8 thermally activated by an increase in temperature to irreversibly interrupt the self-discharge process if the battery is overheating or reaching a dangerous temperature, and in combination with a current interrupter 8 activated by an increase in voltage to irreversibly interrupt the self-discharge process if the battery is overcharged. [Figure 4] 4A-4D show cross-sectional views of a prior art film-type lithium ion battery (FIGS. 4A and 4B) and a film-type lithium ion battery of the present disclosure (FIGS. 4C and 4D). [Diagram 5] 5A-5D show cross-sectional views of a prior art film-type lithium ion battery (FIGS. 5A and 5B) and a film-type lithium ion battery of the present disclosure (FIGS. 5C and 5D). [Figure 6] 6A-6D show cross-sectional views of a prior art film-type lithium ion battery (FIGS. 6A and 6B) and a film-type lithium ion battery of the present disclosure (FIGS. 6C and 6D). [Figure 7] 7A-7D show cross-sectional views of a prior art film-type lithium ion battery (FIGS. 7A and 7B) and a film-type lithium ion battery of the present disclosure (FIGS. 7C and 7D). [Figure 8] 8A-8D show cross-sectional views of a prior art film-type lithium ion battery (FIGS. 8A and 8B) and a film-type lithium ion battery of the present disclosure (FIGS. 8C and 8D). [Figure 9] 9A-9D show cross-sectional views of a prior art film-type lithium ion battery (FIGS. 9A and 9B) and a film-type lithium ion battery of the present disclosure (FIGS. 9C and 9D). [Figure 10] 10A-10D show cross-sectional views of a prior art film-type lithium ion battery (FIGS. 10A and 10B) and a film-type lithium ion battery of the present disclosure (FIGS. 10C and 10D). [Figure 11] 11A-11D show cross-sectional views of a prior art film-type lithium ion battery (FIGS. 11A and 11B) and a film-type lithium ion battery of the present disclosure (FIGS. 11C and 11D). [Figure 12] 12A-12C show an exemplary structure of a combined current limiter 6 and current interrupter 8. FIG. [Figure 13] 13A and 13B show an exemplary cell composition.

[0054] [Figure 14] FIG. 14 shows the various positive electrode 14 formulations used in the chemical decomposition voltage measurements. [Figure 15] Figure 15 shows the baseline resistance of Cell No. 2 at 3.6 V versus graphite as temperature increases. With increasing temperature, the resistance decreases by about 10 times. [Figure 16] 16 shows the resistance of Cell No. 4 (cathode 14 with Al2O3 and CaCO3 ceramic layers) at 0 V and 3.655 V versus graphite with increasing temperature. The resistance increases slightly at zero voltage and increases significantly at 3.646 V and 4.11 V. [Figure 17] 17 shows the resistance of Cell No. 3 (cathode 14 with CaCO3 ceramic layer) at 0 V, 3.646 V and 4.11 V versus graphite with increasing temperature. The resistance increases slightly at zero voltage and significantly at 3.655 V. [Figure 18] FIG. 18 shows the cell voltage vs. discharge capacity of baseline Cell No. 1 (without resistive layer) at 1 A, 3 A, 6 A, and 10 A. [Figure 19] 19 shows the relationship between cell voltage and discharge capacity of baseline cell No. 3 (85.2% CaCO3-based resistive layer 6) at 1 A, 3 A, 6 A, and 10 A. With this particular resistive layer 6, the cell discharge capability decreases significantly with increasing cell discharge current. [Figure 20] Figure 20 summarizes the cell impedance and discharge capacity at 1 A, 3 A, 6 A, and 10 A, and the ratio of the capacity at 3 A, 6 A, or 10 A to the capacity at 1 A for cells No. 1 (reference), 3, 4, 5, and 6. The cell impedance at 1 kHz increases with the presence of the resistive and gassing layers. Although the cell discharge capacity depends on the individual case, the resistive layer 6 resulted in an increase in the cell impedance, as all cells with the resistive layer 6 have a higher impedance. [Figure 21] FIG. 21 shows the impact test. [Figure 22] Figure 22 shows the cell temperature profile during the impact test for cells No. 1 (reference), 3, 5 and 6. When the steel rod impacted the cells, the voltage of all tested cells dropped immediately. All cells with resistance and gas evolution layers passed the test, but the cell without resistance layer 6 failed the test (caught fire). The maximum cell temperatures during the impact test are summarized in Figure 23. [Figure 23] FIG. 23 shows a summary of the maximum cell temperatures in the impact tests for cells No. 1 (reference), 3, 4, 5, and 6. [Figure 24] Figure 24 shows the relationship between shock test time and cell voltage and temperature for cell No. 6. The shock start time is set to 2 minutes. As soon as the shock was applied to the cell, the cell voltage dropped to zero. It can be seen that the cell temperature rose rapidly. [Diagram 25]Figure 25 shows the relationship between overcharge time and cell voltage and temperature for cell No. 3 (without protective layer). The cell voltage gradually increased until 40 minutes, then decreased slightly, and at about 56 minutes jumped abruptly to the maximum charging voltage, while the cell temperature increased significantly to over 600°C. Upon disconnection, the cell voltage and temperature decreased to very small values ​​and the cell ignited. The overcharge current was 2A until the cell ignited, then decreased to 0.2A for 1-2 minutes, and then returned to 2A as the cell shorted. The cell burned. [Figure 26] FIG. 26 shows the relationship between overcharge time and cell voltage and temperature for cell No. 3 (CaCO3 layer). The cell voltage gradually increased until 40 minutes, then increased rapidly to the maximum charging voltage of 12 V at about 55 minutes. The cell temperature rose to above 80°C at about 40 minutes from the start, then decreased rapidly. At 55°C, the overcharge current decreased significantly and remained at 0.2 A for the remainder of the test time. After the test, the cell was noticeably swollen. [Figure 27] FIG. 27 shows the relationship between overcharge time and cell voltage and temperature for cell No. 5 (Na2O7Si3+Al2O3 layers). The cell voltage gradually increased until 40 min, then suddenly increased to the maximum charge voltage of 12 V at about 75 min. The overcharge profile of the cell is significantly different from that of the CaCO3-based resistive layer 6, indicating the difference between the decomposition of CaCO3 and that of Na2O7Si3. The cell temperature significantly increased to above 75° C. at about 40 min from the start, and then gradually decreased. At 75 min, the overcharge current significantly decreased and remained at 1 A for the remainder of the test time. After the test, the cell was noticeably swollen. [Figure 28] FIG. 28 shows a summary of the maximum cell temperatures during the overcharge test (2A / 12V) for cells No. 1 (reference), 3, 4, 5, and 6. [Figure 29] Figure 29 shows the cycle life of cell No. 3 (CaCO3 resistive layer 6). The cell showed a loss of about 1.8% after 100 cycles, which is lower than that of the cells without a resistive layer (on average, ~2.5%, not shown). [Diagram 30]Figure 30 shows the cycle life of cell No. 4 (with CaCO3 and Al2O3 resistive layer 6). The cell showed a loss of about 1.3% after 100 cycles, which is lower than that of the cells without the resistive layer (on average, ~2.5%, not shown). [Diagram 31] Figure 31 shows the current vs. voltage profiles at room temperature for compounds (gas generants) containing different anions that may be used in rechargeable batteries with different operating voltages. The peak current and peak voltage are shown in Figure 32. Cu(NO3)2 had the largest peak current while CaCO3 had the smallest peak current. Cu(NO3)2 had the smallest peak voltage while CaCO3 had the largest peak voltage. Therefore, Cu(NO3)2 is useful for lithium-ion batteries with relatively low operating voltages (typical maximum charging voltage of 3.7 V), such as lithium-ion cells using lithium iron phosphate cathodes. CaCO3 is useful for high operating voltage lithium-ion cells using high voltage cathodes such as lithium cobalt oxide (typical maximum charging voltage of 4.2 V) or lithium nickel cobalt manganese oxide (typical maximum charging voltage of 4.3 or 4.4 V). [Diagram 32] FIG. 32 summarizes the peak currents and peak voltages for compounds containing different anions. [Diagram 33]Figure 33 shows the current vs. voltage profiles for polymers (organic gas generators) with and without different anions that may be used in rechargeable batteries with different operating voltages. PVDF was used as a comparison. Peak currents and peak voltages are shown in Figure 34. Carbopol, AI-50, and PVDF had similar peak currents with the lowest CMC. Carbopol had the lowest peak voltage and the highest CMC. Thus, Carbopol with CO3 2- anion is useful for lithium-ion cells with relatively low operating voltages (typical maximum charge voltage of 3.7 V), such as lithium-ion cells using lithium iron phosphate cathodes. CMCs are useful for high operating voltage lithium-ion cells using high voltage cathodes such as lithium cobalt oxide (typical maximum charge voltage of 4.2 V) or lithium nickel cobalt manganese oxide (typical maximum charge voltage of 4.3 or 4.4 V). Water is one of the CMC decomposition compounds, and not only does it turn into steam or gas at temperatures above 100°C, but it also reacts with the electrolyte and the intercalated lithium in the negative graphite electrode to produce gases such as hydrogen fluoride (HF) and oxygen (O2). [Diagram 34] FIG. 34 summarizes the peak currents and peak voltages with and without different anions. [Diagram 35] FIG. 35 shows the cell temperature and overcharge voltage profiles in a 2A / 12V overcharge test at room temperature. [Diagram 36] FIG. 36 shows the cell impedance and capacity at different currents for cells 1, 3, 4, 5, and 6 described in Examples 9-12 below. [Figure 37] Figure 37 shows the change in resistance at 3.6 V vs. graphite for cell 2 (reference, no resistive layer) with increasing temperature. With increasing temperature, the resistance decreased by about 10 times. [Figure 38] Figure 38 shows the change in resistance at 4.09 V vs. graphite for cell 3 with increasing temperature. With increasing temperature, the resistance decreased slightly, then increased by about 3-fold, then decreased by about 3-fold. [Figure 39] 39 shows the relationship between cell voltage and discharge capacity of cell 4 at 1 A, 3 A, 6 A, and 10 A. With this particular resistive layer, the cell discharge capability decreased significantly with increasing cell discharge current. [Diagram 40] Figure 40 shows the cell temperature profile during impact testing for cells 1, 3, 4, 5, and 6 described in Examples 9-12. All cells with a resistive layer passed the test, while all cells without a resistive layer failed (caught fire). The maximum cell temperature during impact testing is shown in Figure 41. [Diagram 41] FIG. 41 shows the maximum temperatures during impact testing for cells 1, 3, 4, 5, and 6 described in Examples 9-12. [Diagram 42] Figure 42 shows the cycle life of cell 3. After 100 cycles, the cell lost about 2%, which was similar to the value for cells without a resistive layer (on average, ~2.5%, not shown). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0055] High energy density rechargeable batteries, including lithium ion batteries, that are safe and capable of long term operation are a goal of battery manufacturers. One aspect of safe battery operation is controlling the heat generated by a rechargeable battery. As mentioned above, many factors, such as battery damage, accidents, and excessive internal current, can increase the heat generated by a rechargeable battery beyond its heat dissipation capabilities. If the heat generated by a battery exceeds its heat dissipation capabilities, the battery becomes susceptible to thermal runaway, overheating, or even fire or violent explosion. The following describes an apparatus and method related to a thermally actuated internal current interrupter that interrupts the internal circuitry of a rechargeable battery to prevent thermal runaway.

[0056] Another aspect of safe battery operation is to control the reactions at the electrodes of these rechargeable batteries, both during charging and discharging of the battery. As mentioned above, in use, current flows outside the battery through an external circuit, while ions move from one electrode of the battery to the other. In some cases, overcharging can occur, resulting in thermal runaway within the battery. Below, we describe an apparatus and method related to an internal current limiter that limits the rate of internal discharge of a rechargeable battery in the presence of an internal short circuit.

[0057] A further aspect of safe battery operation is to control the discharge of these rechargeable batteries. As mentioned above, in rechargeable batteries, a separator or barrier layer is used to separate the negative and positive electrodes, allowing ions to flow through the battery, but current to flow outside the battery through an external circuit. Many factors can cause the separator to tear, which can lead to a short circuit within the rechargeable battery. A short circuit can result in rapid discharge and possibly overheating and thermal runaway. Below, we describe an apparatus and method related to an internal current limiter that limits the rate of internal discharge of a rechargeable battery in the presence of an internal short circuit.

[0058] The terms used herein are intended to describe only some specific exemplary embodiments and are not intended to limit the disclosure. As used herein, the singular includes the plural unless the context clearly indicates otherwise. The terms "comprises" and / or "comprising" as used herein specify the presence of stated features, integers, steps, operations, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof.

[0059] In this specification, terms such as "first", "second", etc. are used to describe various members, elements, regions, layers, and / or components, but these members, regions, layers, and / or components should not be limited by these terms. These terms are used merely to distinguish one member, element, region, and / or component from another member, element, region, layer, and / or component. Thus, for example, a first member, element, region, layer, and / or component described below can be referred to as a second member, element, region, layer, and / or component without departing from the teachings of the present disclosure.

[0060] 1A-1G are schematic diagrams showing exemplary configurations of film-type lithium-ion batteries with one or more resistive layers (6 in FIGS. 4A-4D) that act as current limiters to protect the battery from overheating in the event of an internal short circuit, and in combination with a thermally activated current interrupter 8, irreversibly interrupts the self-discharge process if the battery overheats or reaches a dangerous temperature. FIGS. 1A and 1C show battery configurations with a cathode current collector 101, a cathode energy layer 102, a separator 103, an anode energy layer 104, a resistive limiter and thermal barrier layer 105, and an anode current collector 106. The configuration shown in FIG. 1B has a cathode current collector 101, a cathode energy layer 102, a separator 103, a first anode energy layer 107, a resistive limiter and thermal barrier layer 105, a second anode energy layer 108, and an anode current collector 106. Figure 1D shows a configuration with a cathode current collector 101, a first cathode energy layer 109, a separator 103, a second cathode energy layer 110, a resistance limiter and thermal barrier layer 105, an anode energy layer 104, and an anode current collector 106. Figures 1E-1G show a battery configuration with a cathode current collector 101, a cathode energy layer 102, a separator 103, an anode energy layer 104, a first resistance limiter and thermal barrier layer 111, a second resistance limiter and thermal barrier layer 112, an anode energy layer 104, and an anode current collector 106.

[0061] 2A and 2B are schematic diagrams showing an exemplary configuration of a film-type lithium-ion battery having one or more layers that function as a combined current limiter 6 and current interrupter 8 to protect the battery from overheating in the event of an internal short circuit, and in combination with a voltage-activated current interrupter 8 due to an increase in voltage, to irreversibly interrupt the self-discharge process if the battery overheats. FIG. 2A shows a battery configuration having an anode current collector 201, an anode energy layer 202, a separator 203, a cathode energy layer 204, a resistance limiter and thermal barrier layer 205, and a cathode current collector 206. The configuration shown in FIG. 2B has an anode current collector 201, an anode energy layer 202, a separator 203, a first cathode energy layer 207, a resistance limiter and thermal barrier layer 205, a second cathode energy layer 208, and a cathode current collector 206.

[0062] 3A and 3B are schematic diagrams showing an exemplary configuration of a film-type lithium-ion battery having one or more resistive layers that act as a current limiter 6 to protect the battery from overheating if an internal short circuit occurs, and in combination with a current interrupter 8 that is thermally activated by an increase in temperature to irreversibly interrupt the self-discharge process if the battery overheats or reaches a dangerous temperature, and in combination with a current interrupter 8 that is activated by an increase in voltage to irreversibly interrupt the self-discharge process if the battery is overcharged. FIG. 3A shows the configuration of the battery having an anode current collector 301, an anode energy layer 302, a separator 303, a cathode energy layer 304, a resistive limiter, thermal and voltage blocking layer 305, and a cathode current collector 306. The configuration shown in FIG. 3B includes an anode current collector 301, an anode energy layer 302, a separator 303, a first cathode energy layer 307, a resistance limiter, thermal and voltage blocking layer 305, a second cathode energy layer 308, and a cathode current collector 306.

[0063] 4C and 4D show the film-type lithium ion battery of FIG. 1A, 2A, or 3A. More specifically, FIGS. 4A-4D show the current flow through a film-type lithium ion battery undergoing a discharge to power a load (L). FIGS. 4A and 4C show the current flow through a film-type lithium ion battery with an intact and fully operational separator 2 (no shorts). FIGS. 4B and 4D show the current flow through a film-type lithium ion battery with a resistive layer acting as a current limiter 6, where the separator 2 is shorted by a conductive dendrite 10 penetrating it. In FIGS. 4B and 4D, the battery is undergoing an internal discharge with a dendrite 10 penetrating the separator 2. Note that current flows from one current collector 4 to the other in the device with a separator 2 without a short (FIGS. 4A and 4C) and in the conventional device with a shorted separator 2 (FIG. 4B). However, in an exemplary device of the present disclosure having a shorted separator 2 and resistive layer 6 (FIG. 4D), the current is diverted away from the current collector 4 and is greatly reduced. In FIG. 4D, the interrupter 8 is not triggered.

[0064] 5C and 5D show the film-type lithium ion battery of FIG. 1A, 2A, or 3A. More specifically, FIGS. 5A-5D show the current flow through the film-type lithium ion battery when it is being charged by a smart power source (PS) and stops charging when an abnormal charging voltage is detected. FIGS. 5A and 5C show the current flow of a film-type lithium ion battery with an intact and fully operational separator 2 (no shorts). FIGS. 5B and 5D show the current flow of a film-type lithium ion battery with a separator 2 shorted by a conductive dendrite 10. Note that in the device with a separator 2 without a short (FIG. 5A and 5C) and the conventional device with a shorted separator 2 (FIG. 5B), the current flows from one current collector 4 to the other current collector. However, in the exemplary device of the present disclosure with a shorted separator 2 and resistive layer 6 (FIG. 5D), the current is diverted away from the current collector 4 and is greatly reduced. In FIG. 5D, the interrupter 8 is not triggered.

[0065] 6C and 6D show the film-type lithium ion battery of FIG. 1A, 2A, or 3A after the interrupter 8 has been triggered due to excessive temperature or voltage. More specifically, FIGS. 6A-6D show the current flow through a film-type lithium ion battery undergoing discharge to power a load (L). FIGS. 6A and 6C show the current flow through a film-type lithium ion battery with an intact and fully operational separator 2 (no shorts). FIGS. 6B and 6D show the current flow through a film-type lithium ion battery shorted by a conductive dendrite 10 penetrating the separator 2. Note that current flows from one current collector 4 to the other in the device with a separator 2 without a short (FIGS. 6A and 6C) and the conventional device with a shorted separator 2 (FIG. 6B). However, in an exemplary device of the present disclosure (FIG. 6D) with a shorted separator 2 and both a resistive layer (current limiter 6) and a current interrupter 8, the current is diverted away from the current collector 4 and greatly reduced. In FIG. 6D, the interrupter 8 has been triggered.

[0066] 7C and 7D show the film-type lithium ion battery of FIG. 1A, 2A, or 3A after the interrupter 8 has been triggered due to excessive temperature or voltage. More specifically, FIG. 7 shows the current flow through the film-type lithium ion battery when it is being charged with a smart power source (PS) that stops charging when it detects an abnormal charging voltage. FIGS. 7A and 7C show the current flow of a film-type lithium ion battery with an intact and fully operational separator 2 (no shorts). FIGS. 7B and 7D show the current flow of a film-type lithium ion battery with a short circuit caused by a separator 2 shorted by a conductive dendrite 10. Note that current flows from one current collector 4 to the other in the device with a separator 2 without a short (FIGS. 7A and 7C) and the conventional device with a shorted separator 2 (FIG. 7B). However, in an exemplary device of the present disclosure (FIG. 7D) with a shorted separator 2 and resistive layer (current limiter 6), the current is diverted away from the current collector 4 and is greatly reduced. In FIG. 7D, the interrupter 8 has been triggered.

[0067] 8C and 8D show the film-type lithium ion cell of FIG. 1A, 2A, or 3A. More specifically, FIGS. 8A-8D show the current flow through a film-type lithium ion cell undergoing a discharge to power a load (L). FIGS. 8A and 8C show the current flow through a film-type lithium ion cell with an intact and fully operational separator 2 (no shorts). FIGS. 8B and 8D show the current flow through a film-type lithium ion cell with a resistive layer acting as a current limiter 6, where the separator 2 is shorted due to a break 16. In FIGS. 8B and 8D, the cell is undergoing an internal discharge due to a tear 16 penetrating the separator 2. Note that current flows from one current collector 4 to the other current collector in the device with a separator 2 without a short (FIGS. 8A and 8C) and in the conventional device with a shorted separator 2 (FIG. 8B). However, in an exemplary device of the present disclosure having a shorted separator 2 and resistive layer 6 (FIG. 8D), the current is diverted away from the current collector 4 and is greatly reduced. In FIG. 8D, the interrupter 8 is not triggered.

[0068] 9C and 9D show the film-type lithium ion battery of FIG. 1A, 2A, or 3A. More specifically, FIGS. 9A-9D show the current flow through the film-type lithium ion battery when it is being charged by a smart power source (PS) and stops charging when an abnormal charging voltage is detected. FIGS. 9A and 9C show the current flow of a film-type lithium ion battery having an intact and fully operational separator 2 (no shorts). FIGS. 9B and 9D show the current flow of a film-type lithium ion battery having a separator 2 shorted by a break 16. Note that in the device having an unshorted separator 2 (FIGS. 9A and 9C) and the conventional device having a shorted separator 2 (FIG. 9B), the current flows from one current collector 4 to the other current collector. However, in the exemplary device of the present disclosure having a shorted separator 2 and resistive layer 6 (FIG. 9D), the current is diverted away from the current collector 4 and is greatly reduced. In FIG. 9D, the interrupter 8 is not triggered.

[0069] 10C and 10D show the film-type lithium ion battery of FIG. 1A, 2A, or 3A after the interrupter 8 has been triggered due to excessive temperature or voltage. More specifically, FIGS. 10A-10D show the current flow through a film-type lithium ion battery undergoing discharge to power a load (L). FIGS. 10A and 10C show the current flow through a film-type lithium ion battery with an intact and fully operational separator 2 (no short circuit). FIGS. 10B and 10D show the current flow through a film-type lithium ion battery with a short circuit due to a break 16. Note that current flows from one current collector 4 to the other in the device with a separator 2 without a short circuit (FIGS. 10A and 10C) and the conventional device with a shorted separator 2 (FIG. 10B). However, in an exemplary device of the present disclosure (FIG. 10D) with a shorted separator 2 and both a resistive layer (current limiter 6) and a current interrupter 8, the current is diverted away from the current collector 4 and greatly reduced. In FIG. 10D, the interrupter 8 has been triggered.

[0070] 11C and 11D show the film-type lithium-ion battery of FIG. 1A, 2A, or 3A after the interrupter 8 has been triggered due to excessive temperature or voltage. More specifically, FIGS. 11A-11D show the current flow through the film-type lithium-ion battery when it is being charged with a smart power source (PS), which stops charging when it detects an abnormal charging voltage. FIGS. 11A and 11C show the current flow of a film-type lithium-ion battery with an intact and fully operational separator 2 (no shorts). FIGS. 11B and 11D show the current flow of a film-type lithium-ion battery with a separator 2 shorted by a break 16. Note that current flows from one current collector 4 to the other in the device with a separator 2 without a short (FIGS. 11A and 11C) and the conventional device with a shorted separator 2 (FIG. 11B). However, in an exemplary device of the present disclosure (FIG. 11D) with a shorted separator 2 and resistive layer (current limiter 6), the current is diverted away from the current collector 4 and is greatly reduced. In FIG. 11D, the interrupter 8 has been triggered.

[0071] FIG. 12A shows a resistive layer 6 with a high percentage of ceramic particles coated with a binder. The interstitial voids between the coated ceramic particles make the resistive layer 6 porous. FIG. 12B shows a resistive layer 6 with a high percentage of ceramic particles bonded together by binder particles. The interstitial voids between the coated ceramic particles make the resistive layer 6 porous. FIG. 12C shows a resistive layer 6 with an intermediate percentage (less than 80%) of ceramic particles held together with a binder. The resistive layer 6 lacks interstitial voids between the coated ceramic particles and is non-porous.

[0072] Current Limiter A first aspect of the present disclosure relates to an improved high energy density HEDR battery of the type having an anode energy layer 12, a cathode energy layer 14, a separator 2 disposed between the anode energy layer 12 and the cathode energy layer 14 to prevent internal discharge, and at least one current collector in electronic communication with one of the anode energy layer or the cathode energy layer. The anode energy layer and the cathode energy layer each have an internal resistivity. The HEDR battery has a preferred temperature range for discharging current and an upper temperature safety limit. In the event of separator failure, an improvement can be used to limit the rate of internal discharge through the failed separator and the resulting Joule heat generation. More specifically, the improvement includes a resistive layer 6 interposed between the separator and one of the current collectors 4 to limit the rate of internal discharge through the failed separator in the event of separator failure. The resistive layer 6 has a constant resistivity at temperatures between the preferred temperature range and the upper temperature safety limit. The constant resistivity of resistive layer 6 is greater than the internal resistivity of either of the energy layers. Resistive layer 6 helps to prevent the battery from reaching temperatures above the upper temperature safety limit in the event of separator failure.

[0073] Some embodiments of the present disclosure include improved high energy density rechargeable batteries of the following types: 1. Two electrodes (12 and 14) of opposite polarity are characterized by a resistivity, a safe operating temperature range, and a safe charging voltage, the two electrodes are at risk of overcharging beyond the safe charging voltage and thereby forming a short circuit, and the two electrodes are at risk of thermal runaway beyond the safe operating temperature range. 2. A separator 2 separating two electrodes and preventing internal discharge between them, said separator being exposed to the risk of formation of a short circuit, said short circuit potentially allowing a sudden internal discharge between said two electrodes, said sudden internal discharge between said two electrodes potentially allowing a sudden generation of Joule heat therefrom, said sudden generation of Joule heat potentially allowing thermal runaway. 3. At least one electrode that uses a current collector 4 for electron transfer. 4. A current limiter 6 which forms an electrical connection between one of the electrodes and its corresponding current collector, said current limiter having a resistivity which resistively blocks current, diverting current away from the associated electrode current collector in the event that the separator forms a short circuit, and reducing the rate of internal discharge between the two electrodes. 5. A current interrupter 8 having an engaged configuration, a disengaged configuration, and a gas generating element for transitioning the current interrupter from the engaged configuration to the disengaged configuration, the gas generating element having a trigger for generating gas, the trigger being selected from the group consisting of a temperature trigger and a voltage trigger, the temperature trigger being activated at a temperature above a safe operating temperature range, and the voltage trigger being activated at a voltage above a safe charging voltage, and in the engaged configuration, the current interrupter electrically couples one of the electrodes to a corresponding current collector by a lamination bond, while in the disengaged configuration, the lamination bond is activated. As the lamination bond peels away, the current interrupter forms a non-conductive gap that interrupts the electrical coupling between the electrode and its corresponding current collector, and the current interrupter initiates operation of the gas generating element in response to a trigger to transition from the engaged configuration to the disengaged configuration, and the generated gas peels away the lamination bond to interrupt the electrical coupling between the electrode and its corresponding current collector, thereby combining the current limiter and the current interrupter to reduce the risk of shorting the separator, overcharging the electrodes, and thermal runaway due to overheating of the electrodes.

[0074] In some embodiments, the current interrupter is temperature triggered.

[0075] In some embodiments, the current interrupter has a layer containing a single temperature initiated gas generating element.

[0076] In some embodiments, the current interrupter is voltage initiated.

[0077] In some embodiments, the current interrupter has a layer containing a single gas generating element that is voltage initiated.

[0078] In some embodiments, the current interrupter is temperature and voltage triggered.

[0079] In some embodiments, the current interrupter has a layer containing a single gas generating element that is temperature and voltage initiated.

[0080] In some embodiments, the current interrupter has two gas generating elements, one temperature activated and the other voltage activated.

[0081] In some embodiments, the current interrupter has a layer containing one or more inorganic gas-generating compounds that generate a gas at a particular temperature or voltage.

[0082] In some embodiments, the inorganic gas-generating compound is selected from the group consisting of CaCO3, La2(CO3)3, Na2SO3, ZnCO3Zn(OH)2, CuCO3Cu(OH)2, and Cu(NO3)2, as disclosed in FIG. 32.

[0083] In some embodiments, the current interrupter has a layer containing one or more organic gas-generating compounds that generate a gas at a particular temperature or voltage.

[0084] In some embodiments, the organic gas-generating compound is selected from the group consisting of Carbopol, Torlon, AI-50, CMC, and PVDF, as disclosed in FIG.

[0085] In some embodiments, the current interrupter has a layer containing inorganic and organic gas generating compounds that generate gas at a specific temperature or voltage.

[0086] In some embodiments of the improved high energy density rechargeable battery, the current limiter and the current interrupter are simultaneously incorporated into a protective layer interposed by lamination between the same electrode and current collector, as disclosed in FIGS. 1A, 1C, and 2A.

[0087] In some embodiments of the improved high energy density rechargeable battery, as disclosed in FIG. 3A, the current limiter and the temperature and voltage triggered current interrupter are simultaneously incorporated into a protective layer interposed by lamination between the same electrode and current collector.

[0088] In some embodiments, the improved high energy density rechargeable battery is of a type including two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, and the improvement includes the following features: As disclosed in FIG. 1E, The current limiter and the current interrupter are simultaneously incorporated into a first protective layer interposed by lamination between the first electrode and the first current collector; and The current limiter and the current interrupter are simultaneously incorporated into a second protective layer that is laminated between the second electrode and the second current collector.

[0089] In some embodiments, the improved high energy density rechargeable battery is of a type including two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, and the improvement includes the following features: As disclosed in FIG. 1F, The current limiter and the current interrupter are simultaneously incorporated into a first protective layer interposed by lamination between the first electrode and the first current collector; and The current limiter and the current interrupter are simultaneously incorporated into a second protective layer that is laminated between the second electrode and the separator.

[0090] In some embodiments, the improved high energy density rechargeable battery is of a type including two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, and the improvement includes the following features: As disclosed in FIG. 1G, The current limiter and the current interrupter are simultaneously incorporated into a first protective layer interposed by lamination between the first electrode and the separator; and The current limiter and the current interrupter are simultaneously incorporated into a second protective layer that is laminated between the second electrode and the second current collector.

[0091] In some embodiments, the improved high energy density rechargeable battery is of a type including two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, the first electrode including a first portion and a second portion, and the second portion of the first electrode being interposed between the first portion of the first electrode and the first current collector, and the improvement includes the following features: 1. the current limiter is laminated between a first portion of the first electrode and a second portion of the first electrode; and 2. A current interrupter is laminated between the second portion of the first electrode and the first current collector.

[0092] In some embodiments, the improved high energy density rechargeable battery includes two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, where the first electrode includes a first portion and a second portion, and the second portion of the first electrode is interposed between the first portion of the first electrode and the first current collector, and the improvement further includes the following features: As disclosed in Figures 1B and 2B, the current limiter and the current interrupter are simultaneously incorporated into a protective layer interposed by lamination between the first portion and the second portion of the first electrode.

[0093] In some embodiments, the improved high energy density rechargeable battery includes two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, where the first electrode includes a first portion and a second portion, and the second portion of the first electrode is interposed between the first portion of the first electrode and the first current collector, and the improvement further includes the following features: As disclosed in FIG. 3B, the current limiter and the current interrupter that initiates operation due to both temperature and voltage are simultaneously incorporated into a protective layer interposed by lamination between the first portion and the second portion of the first electrode.

[0094] In some embodiments, the improved high energy density rechargeable battery is of a type including two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, the second electrode including a first portion and a second portion, the first portion of the second electrode being interposed between the second portion of the second electrode and the second current collector, and the improvement includes the following features: 1. the current limiter is laminated between a first portion of the second electrode and a second portion of the second electrode; and 2. A current interrupter is laminated between the second portion of the second electrode and the second current collector.

[0095] In some embodiments, the improved high energy density rechargeable battery is of a type including two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, the second electrode including a first portion and a second portion, the first portion of the second electrode being interposed between the second portion of the second electrode and the second current collector, and the improvement includes the following features: 1. the current limiter is laminated between a first portion of the second electrode and a second portion of the second electrode; and 2. A current interrupter is laminated between the second portion of the second electrode and the second current collector.

[0096] In some embodiments, the improved high energy density rechargeable battery includes two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, where the first electrode includes a first portion and a second portion, and the first portion of the second electrode is interposed between the second portion of the second electrode and the second current collector, and the improvement further includes the following features: As disclosed in FIG. 1D, the current limiter and the current interrupter are simultaneously incorporated into a protective layer interposed by lamination between the first portion and the second portion of the second electrode.

[0097] In some embodiments, the improved high energy density rechargeable battery is of a type including two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, the first electrode including a first portion and a second portion, and the second portion of the first electrode being interposed between the first portion of the first electrode and the first current collector, and the improvement further includes the following features: 1. a current limiter is laminated between the second portion of the first electrode and the first current collector; and 2. The current interrupter is laminated between the first portion of the first electrode and the second portion of the first electrode.

[0098] In some embodiments, the improved high energy density rechargeable battery is of a type including two current collectors, a first current collector and a second current collector, and two electrodes, a first electrode and a second electrode, and the improvement further includes the following features: 1. The current limiter is laminated between the first electrode and the first current collector; and 2. The current interrupter is laminated between the second electrode and the second current collector.

[0099] In some embodiments, the improved high energy density rechargeable battery is of a type in which each electrode has a temperature range for safe operation and an internal resistivity, the improvement further comprising the following feature: within the temperature range for safe operation, the current limiter has a resistivity greater than the internal resistivity of the electrode with which it is laminated.

[0100] In some embodiments, the improved high energy density rechargeable battery further includes the following features: the current limiter is devoid of a resistivity transition switch at temperatures within a temperature range for safe operation.

[0101] In some embodiments, the improved high energy density rechargeable battery is of a type in which each electrode has a temperature range for standard operation, and the improvement further includes the following feature: the current limiter has a resistivity lower than the internal resistivity of the electrodes within the temperature range for standard operation, and has a resistivity greater than the internal resistivity of the electrodes at temperatures above the temperature range for standard operation.

[0102] In some embodiments, the improved high energy density rechargeable battery is of a type in which each electrode has a temperature range for standard operation, and the improvement further includes the following feature: the current interrupter operates at a temperature above the temperature range for standard operation.

[0103] In some embodiments, the improved high energy density rechargeable battery is of a type in which each electrode has a temperature range for standard operation, and the improvement further includes the following features: the current interrupter operates at a temperature above the temperature range for standard operation and within the temperature range for safe operation.

[0104] In some embodiments, the improved high energy density rechargeable battery is of a type in which each electrode has an internal resistivity within a temperature range for safe operation, and the improvement further includes the following feature: the current limiter has a resistivity within a temperature range for safe operation that is greater than the internal resistivity of the electrode with which it is stacked.

[0105] In some embodiments of the improved high energy density rechargeable battery, the improvement further includes the following features, wherein the current limiter and the current interrupter are simultaneously incorporated into a protective layer interposed by lamination between the same electrode and current collector.

[0106] In some embodiments, the improved high energy density rechargeable battery is of a type in which each electrode has a voltage range for safe operation, and the improvement further includes the following features: the current interrupter operates at a voltage that exceeds the voltage range for standard operation.

[0107] In some embodiments, the improved high energy density rechargeable battery is of a type in which each electrode has a voltage range for normal operation and a voltage range for safe operation, and the improvement further includes the following features: the current interrupter operates at a voltage above the voltage range for normal operation and within the voltage range for safe operation.

[0108] In some embodiments of the improved high energy density rechargeable battery, the improvement further includes the following feature: the current limiter and the current interrupter are simultaneously incorporated into a protective layer interposed by lamination between the same electrode and current collector.

[0109] Another embodiment of the present disclosure includes an improved high energy density rechargeable (HEDR) battery, the rechargeable battery comprising two electrodes of opposite polarity, a separator separating the two electrodes, and at least one current collector electrically coupled to one of the electrodes, the separator preventing internal discharge between the two electrodes, and breakage of the separator potentially resulting in internal discharge between the two electrodes (as shown in FIGS. 6A-6B and 7A-7B ), the internal discharge resulting in Joule heat generation as a potential hazard, the improvement including: 1. A thermally actuated current interrupter and a voltage actuated current interrupter, the thermally actuated current interrupter can be laminated between one of the current collectors and one of the electrodes by lamination, the thermally actuated current interrupter electrically couples the current collector to the electrode with which it is laminated when inactive, and peels off from the current collector forming a non-conductive gap to electrically isolate the current collector from the electrode with which it is laminated when active (as shown in Figures 6C-6D and 7C-7D), the electrical isolation slowing down the rate of internal discharge between the two electrodes in case of separator damage; 2. A voltage-activated current interrupter can be laminated between one of the current collectors and one of the electrodes by a lamination method, which when inactive, electrically couples the current collector to the electrode with which it is laminated, and when active, peels off from the current collector forming a non-conductive gap to electrically isolate the current collector from the electrode with which it is laminated, and the electrical isolation slows down the rate of internal discharge between the two electrodes in case of separator damage (as shown in Figures 6C-6D and 7C-7D); Thereby, in the event of separator failure, activation of either a thermally activated current interrupter or a voltage activated current interrupter can slow the generation of Joule heat to reduce potential hazards.

[0110] Some embodiments of the present disclosure include a method of avoiding thermal runaway in a high energy density rechargeable battery undergoing internal discharge due to separator failure, the method comprising peeling an electrode in the battery from a current collector by generating gas from a thermally sensitive gas generating material in a barrier layer interposed between the electrode and the current collector, said peeling electrically isolating the electrode from the current collector to slow the rate of internal discharge.

[0111] Some embodiments of the present disclosure include a method for avoiding thermal runaway within a high energy density rechargeable battery that may suffer separator damage due to voltage overcharge (as shown in FIGS. 7A-7B ), comprising peeling an electrode from a current collector in the battery by generating gas from a voltage sensitive gas generating material in a barrier layer interposed between the electrode and the current collector, said peeling electrically isolating the electrode from the current collector to interrupt voltage overcharge (as shown in FIGS. 7C-7D ).

[0112] The following abbreviations have the following meanings: Carbopol®-934 = Cross-linked polyacrylate polymer supplied by Lubrizol Advanced Materials CMC = Carboxymethylcellulose CMC-DN-800H = CMC in which the sodium salt of the carboxymethyl group has been replaced with ammonium (supplied by Daicel Fine Chemicals) MCMB = Mesocarbon Microbeads NMC = Nickel, Manganese, and Cobalt NMP = N-methylpyrrolidone PTC = Positive Temperature Coefficient PVDF = Polyvinylidene fluoride SBR = Styrene butadiene rubber Super® P = Conductive carbon black supplied by Timcal Corporation Torlon® AI-50 = Water soluble derivative of Torlon 4000TF Torlon® 4000TF = Pure resin polyamide-imide (PAI) powder

[0113] The method of fabricating the resistive layer and the electrode active layer is described below along with the assembly of the battery cell.

[0114] The general process for fabricating the resistive layer (first layer) is as follows: i. Dissolving the binder in a suitable solvent. ii. Adding conductive additives and ceramic powder to the binder solution. iii. The slurry prepared in step ii is applied onto a surface of a metal foil and then dried to form a resistive layer on the surface of said metal foil.

[0115] The general procedure for electrode fabrication (on top of the first layer) is as follows: i. Dissolving the binder in a suitable solvent. ii. Adding conductive additives and ceramic powder to the binder solution. iii. Adding the cathode material or the anode material into the slurry prepared in step v and mixing to form a slurry for electrode coating. iv. The electrode slurry prepared in step vi is applied onto the surface of the layer obtained in step iii. v. Compress the electrode to the desired thickness.

[0116] The general steps in cell assembly are as follows: i. Dry the positive electrode at 125°C for 10 hours and the negative electrode at 140°C for 10 hours. ii. Punching out the electrodes into individual pieces with electrode tabs. iii. Laminating the positive and negative electrodes with a separator as an intermediate layer. iv. Place the jelly roll prepared in step xi into an aluminum composite bag.

[0117] A general procedure for performing an impact test as shown in FIG. 21 on the battery cells described herein is as follows. i. Charge the cell at 2A, 4.2V for 3 hours. ii. Place the cell on a hard, flat surface such as concrete. iii. Attach a thermocouple to the surface of the cell with high temperature tape and connect the positive and negative tabs to a voltmeter. iv. Place a steel rod (diameter 15.8 mm ± 0.1 mm, length approximately 70 mm) with its side across the centre of the cell. v. A 9.1±0.46 kg steel block (75 mm diameter, 290 mm height) is suspended at a height of 610±25 mm above the cell. vi. Protect the steel block with a containment tube (8 cm internal diameter) and release it within the tube, allowing it to fall freely onto a steel rod lying on the surface of the cell, breaking the separator while recording the temperature. vii. The steel rod and steel block are left on the surface of the cell so that the temperature of the cell can stabilize near room temperature. viii.End of exam.

[0118] The general steps for performing an overcharge test are as follows: i. Charge the cell at 2A, 4.2V for 3 hours. ii. Place the charged cell in a room temperature oven. iii. Connect the cell to a power source (Hewlett-Packard). iv. Set the power supply voltage and current to 12V and 2A. v. Switch on the power supply and perform an overcharge test while recording the temperature and voltage. vi. The test is terminated when the cell temperature has decreased and stabilized near room temperature.

[0119] The general steps for performing a resistance measurement test are as follows: i. Place a square of copper foil (4.2 x 2.8 cm) with a tab on a metal plate (~12 x ~8 cm). Next, cut a small piece of thermal tape and carefully cover the square of copper foil. ii. Cut a small electrode so that it is slightly larger than the copper foil. Place the electrode on top of the copper foil. iii. Place another copper foil (4.2 x 2.8 cm) with a tab on the surface of the electrode and repeat steps i-ii with it. iv. At this point, pack them together, cover with high temperature tape and remove any air bubbles. v. Cut out the V-shaped metal pieces from both tabs. Attach the metal clamps to the finished strip and tighten them with screws. Make sure the screws are tight. vii. Attach the tabs to the connectors of a Battery HiTester (HIOKI USA) and measure the resistance to ensure that a good sample has been prepared for measurement. viii. Place the metal clamp into the oven, connect the V-shaped tab to the connector and tighten the screw. Tape the thermocouple onto the metal clamp. ix. Attach the wires from the oven to the Battery HiTester. Be careful not to mix up the positive and negative wires. x. Close the oven and ramp the temperature to 200° C. at 4° C. / min and start the test. Record data every 15 seconds. xi. Stop recording data when the temperature of the metal clamp and oven just exceeds 200°C. xii. Switch off the oven and the Battery HiTester. xiii.End of exam.

[0120] The general steps for performing the cycle life test procedure are as follows: i. Rest for 5 minutes. ii. Discharge at 1A to 2.8V. iii. Rest for 20 minutes. iv. Charge at 0.7A for 270 minutes to 4.2V. v. Pause for 10 minutes. Discharge to 2.8V at vi.0.7A. vii. Rest for 10 minutes. viii. Repeat steps iii to vii 100 times. ix.End of Exam.

[0121] The general steps for discharge testing at 1A, 3A, 6A, and 10A for battery cells with resistive layers are as follows: i. Rest for 5 minutes. ii. Discharge at 1A to 2.8V. iii. Rest for 20 minutes. iv. Charge at 0.7A for 270 minutes to 4.2V. v. Pause for 10 minutes. Discharge to 2.8V at vi.1A. vii. Rest for 10 minutes. viii.Charge at 0.7A for 270 minutes to 4.2V. ix. Rest for 10 minutes. Discharge at x.3A to 2.8V. xi.Charge at 0.7A for 270 minutes to 4.2V. xii. Rest for 10 minutes. xiii.Discharge at 6A to 2.8V. xiv. Charge at 0.7A for 270 minutes to 4.2V. xv. Rest for 10 minutes. xvi.Discharge at 10A to 2.8V. xvii. Rest for 10 minutes. xviii.End of exam.

[0122] definition Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs. In the event that there are a plurality of definitions for terms herein, those in this section prevail unless stated otherwise.

[0123] As used herein, "high energy density rechargeable (HEDR) batteries" refers to batteries that are capable of storing relatively large amounts of electrical energy per unit weight, on the order of about 50 W-hr / kg or more, and that are designed for reuse and can be recharged after repeated use. Non-limiting examples of HEDR batteries include metal-ion batteries and metal batteries.

[0124] As used herein, "metal ion battery" refers to any type of rechargeable battery in which metal ions move from the negative electrode to the positive electrode during discharge and vice versa during charging. Non-limiting examples of metal ion batteries include lithium ion, aluminum ion, potassium ion, sodium ion, magnesium ion, and others.

[0125] As used herein, "metal ion battery" refers to any type of rechargeable battery in which the anode is a metal or metal alloy. The anode may be solid or liquid. Metal ions migrate from the negative electrode to the positive electrode during discharge and vice versa during charging. Non-limiting examples of metal batteries include MS, M-NiCl2, M-V2O5, M-Ag2VP2O8, M-TiS2, M-TiO2, M-MnO2, M-Mo3S4, M-MoS6Se2, M-MoS2, M-MgCoSiO4, M-Mg 1.03 Mn 0.97 SiO4, and others, where M=Li, Na, K, Mg, Al, or Zn.

[0126] As used herein, "lithium ion battery" refers to any type of rechargeable battery in which lithium ions move from the negative electrode to the positive electrode during discharge and vice versa during charging. Non-limiting examples of lithium ion batteries include lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFeO4), lithium cobalt phosphate (LiCoPO4), lithium-rich layered oxides such as (LiMnO3)x(LiMO2) (M=Ni, Co, Mn), olivine, LiMSiO4 (M=iron, cobalt, nickel, and vanadium), lithium manganese oxide (LiMn2O4), lithium nickel oxide (LiNiO2), lithium nickel manganese cobalt oxide (LiNiMnCoO2), lithium nickel cobalt aluminum oxide (LiNiCoAlO2), lithium titanate (Li4Ti5O4), lithium phosphate (LiFeO4), lithium cobalt oxide (LiCoPO4), lithium phosphate (LiCoPO4), lithium cobalt oxide ... 12), lithium dititanate, lithium / graphene, lithium / graphene oxide coated sulfur, lithium-sulfur, lithium-purpurin, and others. Lithium ion batteries can also have a variety of anodes, including silicon-carbon nanocomposite anodes, and others. Lithium ion batteries can be in a variety of shapes, including small cylindrical (solid without terminals), large cylindrical (solid with large screw terminals), prismatic (semi-rigid plastic case with large screw terminals), and pouch (soft flat body). Lithium ion batteries can be in soft packaging or pouches. The electrolyte in these batteries can be liquid electrolyte (such as carbonate-based or ionic), solid electrolyte, polymer-based electrolyte, or a mixture of these electrolytes.

[0127] As used herein, "aluminum ion battery" refers to any type of rechargeable battery in which aluminum ions move from the negative electrode to the positive electrode during discharge and vice versa during charging. Non-limiting examples of aluminum ion batteries include Al n M2(XO4)3, where X=Si, P, S, Mo, As, etc., and M=Fe, Ca, Mg, V, Cr, etc., and Al x (V4O8),Al x NiS2,Al x FeS2,Al x VS2,Al x Aluminum transition metal oxides such as WS2 (Al x MO2, where M=Fe, Mn, Ni, Mo, Co, Cr, Ti, V, etc.

[0128] As used herein, "potassium ion battery" refers to any type of rechargeable battery in which potassium ions move from the negative electrode to the positive electrode during discharge and vice versa during charging. Non-limiting examples of potassium ion batteries include K n M2(XO4)3, where X=Si, P, S, Mo, As, etc., and M=Fe, Ca, Mg, V, Cr, etc., and potassium transition metal oxides (KMO2, where M=Fe, Mn, Ni, Mo, Co, Cr, Ti, V, etc.).

[0129] As used herein, "sodium ion battery" refers to any type of rechargeable battery in which sodium ions move from the negative electrode to the positive electrode during discharge and vice versa during charging. Non-limiting examples of sodium ion batteries include Na n M2(XO4)3, where X = Si, P, S, Mo, As, etc., and M = Fe, Ca, Mg, V, Cr, etc.; NaV 1-x Cr x PO4F, NaVPO4F, Na4Fe3(PO4)2(P2O7), Na2FePO4F, Na2FeP2O7, Na 2 / 3 [Fe 1 / 2 Mn 1 / 2 ]O2, Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 )O2, NaTiS2, NaFeF3;Na 2 / 3 [Fe 1 / 2 Mn 1 / 2 ]O2, Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 )O2, Na x Mo2O4, NaFeO2, Na 0.7 CoO2, NaCrO2, NaMnO2, N a0.44 MnO2, Na 0.7 MnO2, Na 0.7 MnO 2.25 , Na 2 / 3 Mn 2 / 3 Ni 1 / 3 O2, Na 0.61 Ti 0.48 Mn 0.52 Sodium transition metal oxides such as O2 (NaMO2, where M = Fe, Mn, Ni, Mo, Co, Cr, Ti, V, etc.); Na 1+x V3O8, Na x V2O5, and Na x Vanadium oxides such as VO2 (x=0.7,1) are included.

[0130] As used herein, "magnesium ion battery" refers to any type of rechargeable battery in which magnesium ions move from the negative electrode to the positive electrode during discharge and vice versa during charging. Non-limiting examples of magnesium ion batteries include Mg n M2(XO4)3, where X=Si, P, S, Mo, As, etc., and M=Fe, Ca, Mg, V, Cr, etc.; magnesium transition metal oxides (MgMO2, where M=Fe, Mn, Ni, Mo, Co, Cr, Ti, V, etc.).

[0131] As used herein, "silicon ion battery" refers to any type of rechargeable battery in which silicon ions move from the negative electrode to the positive electrode during discharge and vice versa during charging. Non-limiting examples of silicon ion batteries include Si n M2(XO4)3, where X=Si, P, S, Mo, As, etc., and M=Fe, Ca, Mg, V, Cr, etc.; silicon transition metal oxides (SiMO2, where M=Fe, Mn, Ni, Mo, Co, Cr, Ti, V, etc.).

[0132] As used herein, "binder" refers to any material that provides mechanical adhesion and unlimited tolerance to large volume changes. Non-limiting examples of binders include styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVDF)-based binders, carboxymethyl cellulose (CMC)-based binders, polyacrylic acid (PAA)-based binders, polyvinyl acid (PVA)-based binders, poly(vinylpyrrolidone) (PVP)-based binders, and the like.

[0133] As used herein, "conductive additive" refers to any material that increases the electrical conductivity of a material. Non-limiting examples of conductive additives include carbon black additives, graphite non-aqueous ultrafine carbon (UFC) suspensions, carbon nanotube composite (CNT) additives (single and multi-walled), carbon nano-onion (CNO) additives, graphene-based additives, reduced graphene oxide (rGO), conductive acetylene black (AB), conductive poly(3-methylthiophene) (PMT), fibrous nickel powder additives, aluminum powder, and electrochemically active oxides such as lithium nickel manganese cobalt oxide.

[0134] As used herein, "metal foil" refers to any metal foil that is stable under high voltage. Non-limiting examples of metal foils include aluminum foil, copper foil, titanium foil, steel foil, nanocarbon paper, graphene paper, carbon fiber sheet, etc.

[0135] As used herein, "ceramic powder" means any unsintered electrical insulator or conductor. Non-limiting examples of ceramic powders include barium titanate (BaTiO3), barium zirconium titanate, strontium titanate (SrTiO3), calcium titanate (CaTiO3), magnesium titanate (MgTiO3), calcium magnesium titanate, zinc titanate (ZnTiO3), lanthanum titanate (LaTiO3), neodymium titanate (Nd2Ti2O7), barium zirconate (BaZrO3), calcium zirconate (CaZrO3), and lanthanum titanate (LaTiO3). ), lead magnesium niobate, lead zinc niobate, lithium niobate (LiNbO3), barium stannate (BaSnO3), calcium stannate (CaSnO3), magnesium aluminum silicate, sodium silicate (NaSiO3), magnesium silicate (MaSiO3), barium tantalate (BaTa2O6), niobium oxide, zirconium tin titanate, silicon dioxide (SiO2), aluminum oxide (Al2O3), titanium dioxide (TiO2), etc.

[0136] As used herein, "gas generating material" means any material that decomposes at high temperature or voltage to generate gas, either directly from the gas generating material or indirectly from the reaction of the gas generating material with other materials contained within the battery (e.g., the electrolyte and electrodes) to generate decomposition products. Non-limiting examples of gas generating materials include M n (CO3) m , M n (SO3) m , M n (NO3) m , 1 M n 2 M n (CO3)m, NaSiO3 * H2O, inorganic carbonates such as CuCO3Cu(OH)2, and polymethacrylates [-CH2-C(CH3)(COOM)-] p and polyacrylate [-CH2-CH(COOM)-] p Organic carbonates such as M, 1 M. 2 M is independently selected from the group consisting of Ba, Ca, Cd, Co, Cu, Fe, K, Li, Mg, Mn, Na, Ni, Pb, Sr, and Zn, n is 1-3, and m is 1-4. In some embodiments, M is independently selected from the group consisting of ammonium ions, pyridinium ions, and quaternary ammonium ions. In some embodiments, the gas generating material may decompose to produce a liquid (e.g., water). The liquid may react with another material contained within the battery to form a gas that strips the electrode and the cell (e.g., water may react with the electrolyte [LiFP6] to form gaseous HF and lithium at the negative electrode and generate hydrogen gas (H2). If the temperature of the cell exceeds the vaporization temperature of the liquid, the liquid may undergo a phase change to form a gas that also strips the electrode.

[0137] The layer was applied onto the metal foil by an automatic coater (Compact Coater, model no. 3R250W-2D) manufactured by Thank Metals Co., Ltd. The layer was then compressed to the desired thickness using a calendaring machine (model no. X15-300-1-DZ) manufactured by Beijing Sevenstar Huachuang Electronics Co., Ltd. EXAMPLES

[0138] The present disclosure will be described in more detail using the following examples, but the present disclosure is not limited to the examples shown below.

[0139] Example 1 The preparation of the reference electrode, the positive electrode, and the negative electrode, as well as the preparation of the completed cell No. 1 used for the resistance measurement, the discharge capacity test at 50° C., the impact test, and the evaluation of the cycle life are described below.

[0140] A) Preparation of POS1A as an example of positive electrode preparation i) PVDF (21.6 g) was dissolved in NMP (250 g); ii) Carbon black (18 g) was added and mixed at 6500 rpm for 15 minutes; iii) LiNi 0.5 Mn 0.3 Co 0.2 O2(NMC) (560.4 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) some NMP was added to adjust the viscosity; v) The slurry was coated onto 15 μm thick aluminum foil using an automated coater with a first heating zone set at about 80° C. and a second heating zone set at about 130° C., and the NMP was allowed to evaporate. The final solid loading was about 15.55 mg / cm 2 The cathode layer was then compressed to a thickness of about 117 μm. The fabricated electrode was used for impedance measurements at 0 V versus temperature, taken as zero voltage against a standard graphite electrode, and dried for cell assembly.

[0141] B) Preparation of NEG2A as an example of negative electrode preparation i) CMC (5.2 g) was dissolved in deionized water (~300 g); ii) Carbon black (8.4 g) was added and mixed at 6500 rpm for 15 minutes; iii) Activated graphite for the anode (JFE Chemical Corporation, graphitized mesophase carbon microbeads (MCMB) and synthetic graphite (TIMCAL)) (total 378.4 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (16.8 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 5 minutes; v) Viscosity adjusted for smooth application; vi) The slurry was coated onto a 9 μm thick copper foil using an automated coater with a first heating zone set at about 70° C. and a second heating zone set at about 100° C., and the water was allowed to evaporate. The final solid loading was about 9.14 mg / cm. 2 The negative electrode layer was then compressed to a thickness of about 117 μm. The fabricated negative electrode was dried for cell assembly.

[0142] C) Preparation of cells for evaluation i) Electrodes were punched out to produce individual pieces having electrode tabs; ii) the positive electrode was dried at 125°C for 10 hours and the negative electrode was dried at 140°C for 10 hours; iii) A positive electrode and a negative electrode are laminated with a separator as an intermediate layer; iv) The jelly roll prepared in step iii was laid flat in an aluminum composite bag; v) The bags from step iv were dried in a vacuum oven at 70°C; vi) The bag from step v was filled with an organic carbonate based electrolyte containing LiPF6; vii) the bag from step vi was sealed; viii) left to stand for 16 hours; ix) The cells were charged at C / 20 rate to 4.2V for 5 hours, then charged at 0.5C rate to 4.2V for 2 hours, then rested for 20 minutes, then discharged at 0.5C rate to 2.8V. The cells were punctured under vacuum to release gases and then resealed. The fabricated cells were used for evaluation and other tests such as discharge capability test at 50°C, shock test, cycle life test, etc.

[0143] FIG. 15 shows the change in resistance with increasing temperature for the cathode recovered by autopsying a 3.6 V cell. The resistance decreased by about 10 times. FIG. 18 shows the discharge capacity at discharge currents of 1, 3, 6, and 10 A. FIG. 20 shows the cell impedance at 1 kHz, the capacity at currents of 1, 3, 6, and 10 A, and the ratio of the capacity at 3, 6, and 10 A to the capacity at 1 A. FIG. 22 shows the temperature profile of the cell during the shock test. FIG. 23 shows the maximum temperature of the cell during the shock test. The cell caught fire during the shock test. FIG. 25 shows the voltage and temperature profile of the cell during the overcharge test at 12 V / 2 A. The cell caught fire during the overcharge test (FIG. 28).

[0144] Example 2 The following describes the preparation of the CaCO3-based gas generating agent, the resistance layer, the positive electrode, and the negative electrode, as well as the preparation of the completed cell No. 3 used for resistance measurement, discharge capacity test at 50°C, impact test, and cycle life evaluation.

[0145] A) Positive electrode POS3B as an example of gas generating agent and resistance layer (first layer) preparation i) Torlon® 4000TF (0.8 g) was dissolved in NMP (10 g); ii) PVDF (4.8 g) was dissolved in NMP (~70 g); iii) the solutions prepared in steps i and ii were mixed, then carbon black (0.32 g) was added and mixed at 6500 rpm for 10 minutes; iv) Nano CaCO3 powder (34.08 g) was added to the solution prepared in step iii and mixed at 6500 rpm for 20 minutes to make a flowable slurry; v) The slurry was coated onto 15 μm thick aluminum foil using an automated coater with a first heating zone set at about 135° C. and a second heating zone set at about 165° C., and the NMP was allowed to evaporate. The final solid loading was about 1 mg / cm. 2 It was.

[0146] B) Preparation of POS3A as an example of positive electrode preparation (second layer) i) PVDF (21.6 g) was dissolved in NMP (250 g); ii) Carbon black (18 g) was added and mixed at 6500 rpm for 15 minutes; iii) LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NMC) (560.4 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) some NMP was added to adjust the viscosity; v) The slurry was coated onto POS3B (Example 2A) using an automated coater with a first heating zone set at about 85° C. and a second heating zone set at about 135° C., and the NMP was allowed to evaporate. The final solids loading was about 19.4 mg / cm 2 The positive electrode layer was then compressed to a thickness of about 153 μm. The fabricated electrode was used for impedance measurements at 0 V, which was taken as zero voltage against a standard graphite electrode, to examine the relationship with temperature.

[0147] C) Preparation of NEG3A as an example of negative electrode preparation i) CMC (13 g) was dissolved in deionized water (~1000 g); ii) Carbon black (20 g) was added and mixed at 6500 rpm for 15 minutes; iii) Activated graphite for the anode (JFE Chemical Corporation, graphitized mesophase carbon microbeads (MCMB) and synthetic graphite (TIMCAL)) (total 945.92 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (42 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 5 minutes; v) Viscosity adjusted for smooth application; vi) The slurry was coated onto a 9 μm thick copper foil using an automated coater with a first heating zone set at about 100° C. and a second heating zone set at about 130° C., and the water was allowed to evaporate. The final solids loading was about 11.8 mg / cm. 2 The negative electrode layer was then compressed to a thickness of about 159 μm. The fabricated negative electrode was dried for cell assembly.

[0148] D) Preparation of cells for evaluation i) Electrodes were punched out to produce individual pieces having electrode tabs; ii) the positive electrode was dried at 125°C for 10 hours and the negative electrode was dried at 140°C for 10 hours; iii) A positive electrode and a negative electrode are laminated with a separator as an intermediate layer; iv) The jelly roll prepared in step iii was laid flat in an aluminum composite bag; v) The bags from step iv were dried in a vacuum oven at 70°C; vi) The bag from step v was filled with an organic carbonate based electrolyte containing LiPF6; vii) the bag from step vi was sealed; viii) left to stand for 16 hours; ix) The cell was charged at a rate of C / 50 to 4.2V for 8 hours, then charged at a rate of 0.5C to 4.2V for 2 hours, then rested for 20 minutes, then discharged at a rate of 0.5C to 2.8V; x) The cells were punctured under vacuum to release the gases and then resealed. The fabricated cells were used for evaluation and other tests such as discharge capability test at 50°C, impact test, cycle life test etc.

[0149] FIG. 16 shows the change in resistance with increasing temperature for the positive electrodes recovered from disassembled cells at 0, 3.6, and 4.09 V. The resistance increased with increasing temperature, especially for the positive electrodes obtained from the cells with voltages of 3.66 V and 4 V. FIG. 19 shows the discharge capacity at 1, 3, and 6 A at 50° C. With increasing current, the cell capacity decreased significantly, indicating a strong influence from the resistive layer. FIG. 20 shows the cell impedance at 1 kHz, the capacity at currents of 1 A, 3 A, 6 A, and 10 A, and the ratio of the capacity at 3, 6, and 10 A to the capacity at 1 A. FIG. 26 shows the overcharge profile during the overcharge test. FIG. 28 shows the maximum temperature of the cell during the overcharge test and the residual current at the end of the overcharge test. FIG. 29 shows the discharge capacity with respect to the number of cycles. The cell lost about 1% capacity, which is about 100% better than that of the reference cell (2.5%). Figure 22 shows the temperature profile of the cell during the impact test, and Figure 23 shows the maximum temperature of the cell during the impact test.

[0150] Example 3 The following describes the preparation of the gas generating agent containing 50% Al2O3 and 50% CaCO3, the resistance layer, the positive electrode, and the negative electrode, as well as the preparation of the completed cell No. 4 used for resistance measurement, discharge capacity test at 50°C, impact test, and cycle life evaluation.

[0151] A) Positive electrode POS4B as an example of gas generating agent and resistance layer (first layer) preparation i) Torlon® 4000TF (0.8 g) was dissolved in NMP (10 g); ii) PVDF (4.8 g) was dissolved in NMP (~70 g); iii) the solutions prepared in steps i and ii were mixed, then carbon black (0.32 g) was added and mixed at 6500 rpm for 10 minutes; iv) Nano CaCO3 powder (17.04 g) and Al2O3 powder (17.04 g) were added to the solution prepared in step iii and mixed at 6500 rpm for 20 minutes to make a flowable slurry; v) The slurry was coated onto 15 μm thick aluminum foil using an automated coater with a first heating zone set at about 135° C. and a second heating zone set at about 165° C., and the NMP was allowed to evaporate. The final solid loading was about 1 mg / cm. 2 It was.

[0152] B) Preparation of POS4A as an example of positive electrode preparation (second layer) i) PVDF (21.6 g) was dissolved in NMP (250 g); ii) Carbon black (18 g) was added and mixed at 6500 rpm for 15 minutes; iii) LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NMC) (560.4 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) some NMP was added to adjust the viscosity; v) The slurry was coated onto POS4B (Example 3A) using an automated coater with a first heating zone set at about 85° C. and a second heating zone set at about 135° C., and the NMP was allowed to evaporate. The final solids loading was about 19.4 mg / cm 2 The positive electrode layer was then compressed to a thickness of about 153 μm. The fabricated electrode was used for impedance measurements at 0 V, which was taken as zero voltage against a standard graphite electrode, to examine the relationship with temperature.

[0153] C) Preparation of NEG4A as an example of negative electrode preparation i) CMC (13 g) was dissolved in deionized water (~1000 g); ii) Carbon black (20 g) was added and mixed at 6500 rpm for 15 minutes; iii) Activated graphite for the anode (JFE Chemical Corporation, graphitized mesophase carbon microbeads (MCMB) and synthetic graphite (TIMCAL)) (total 945.92 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (42 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 5 minutes; v) Viscosity adjusted for smooth application; vi) The slurry was coated onto a 9 μm thick copper foil using an automated coater with a first heating zone set at about 100° C. and a second heating zone set at about 130° C., and the water was allowed to evaporate. The final solids loading was about 11.8 mg / cm. 2 The negative electrode layer was then compressed to a thickness of about 159 μm. The fabricated negative electrode was dried for cell assembly.

[0154] D) Preparation of cells for evaluation i) Electrodes were punched out to produce individual pieces having electrode tabs; ii) the positive electrode was dried at 125°C for 10 hours and the negative electrode was dried at 140°C for 10 hours; iii) A positive electrode and a negative electrode are laminated with a separator as an intermediate layer; iv) The jelly roll prepared in step iii was laid flat in an aluminum composite bag; v) The bags from step iv were dried in a vacuum oven at 70°C; vi) The bag from step v was filled with an organic carbonate based electrolyte containing LiPF6; vii) the bag from step vi was sealed; viii) left to stand for 16 hours; ix) The cell was charged at a rate of C / 50 to 4.2V for 8 hours, then charged at a rate of 0.5C to 4.2V for 2 hours, then rested for 20 minutes, then discharged at a rate of 0.5C to 2.8V; x) The cells were punctured under vacuum to release the gases and then resealed. The fabricated cells were used for evaluation and other tests such as discharge capability test at 50°C, impact test, cycle life test etc.

[0155] Figure 20 shows the cell impedance at 1 kHz, the capacity at currents of 1 A, 3 A, 6 A, and 10 A, and the ratio of the capacity at 3, 6, and 10 A to the capacity at 1 A. Figure 22 shows the cell temperature profile during the shock test. Figure 23 shows the maximum cell temperature during the shock test. Figure 26 shows the overcharge profile during a 12 V / 2 A overcharge test. Figure 28 shows the maximum cell temperature during the overcharge test.

[0156] Example 4 The following describes the preparation of the gas generating agent, which is a mixture of Al2O3 and sodium silicate (NaSiO3), the resistance layer, the positive electrode, and the negative electrode, as well as the preparation of the completed cell No. 5 used for resistance measurement, discharge capacity test at 50°C, impact test, and cycle life evaluation.

[0157] A) Positive electrode POS5B as an example of gas generating agent and resistance layer (first layer) preparation i) Torlon® 4000TF (0.8 g) was dissolved in NMP (~10 g); ii) PVDF (4.8 g) was dissolved in NMP (60 g); iii) the solutions prepared in steps i and ii were mixed, then carbon black (0.32 g) was added and mixed at 6500 rpm for 10 minutes; iv) Nano Al2O3 powder (17.04 g) and NaSiO3 (17.04 g) were added to the solution prepared in step iii and mixed at 6500 rpm for 20 minutes to make a flowable slurry; v) The slurry was coated onto 15 μm thick aluminum foil using an automated coater with a first heating zone set at about 135° C. and a second heating zone set at about 165° C., and the NMP was allowed to evaporate. The final solid loading was about 0.7 mg / cm. 2 It was.

[0158] B) Preparation of POS5A as an example of positive electrode preparation (second layer) i) PVDF (21.6 g) was dissolved in NMP (270 g); ii) Carbon black (18 g) was added and mixed at 6500 rpm for 15 minutes; iii) LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NMC) (560.4 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) some NMP was added to adjust the viscosity; v) The slurry was coated onto POS5B (Example 4A) using an automated coater with a first heating zone set at about 85° C. and a second heating zone set at about 135° C., and the NMP was allowed to evaporate. The final solids loading was about 19.4 mg / cm 2 The positive electrode layer was then compressed to a thickness of about 153 μm. The fabricated electrode was used for impedance measurements at 0 V, which was taken as zero voltage against a standard graphite electrode, to examine the relationship with temperature.

[0159] C) Preparation of NEG5A as an example of negative electrode preparation i) CMC (13 g) was dissolved in deionized water (~1000 g); ii) Carbon black (20 g) was added and mixed at 6500 rpm for 15 minutes; iii) Activated graphite for the anode (JFE Chemical Corporation, graphitized mesophase carbon microbeads (MCMB) and synthetic graphite (TIMCAL)) (total 945.92 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (42 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 5 minutes; v) Viscosity adjusted for smooth application; vi) The slurry was coated onto a 9 μm thick copper foil using an automated coater with a first heating zone set at about 100° C. and a second heating zone set at about 130° C., and the water was allowed to evaporate. The final solids loading was about 11.8 mg / cm. 2 The negative electrode layer was then compressed to a thickness of about 159 μm. The fabricated negative electrode was dried for cell assembly.

[0160] D) Preparation of cells for evaluation i) Electrodes were punched out to produce individual pieces having electrode tabs; ii) the positive electrode was dried at 125°C for 10 hours and the negative electrode was dried at 140°C for 10 hours; iii) A positive electrode and a negative electrode are laminated with a separator as an intermediate layer; iv) The jelly roll prepared in step iii was laid flat in an aluminum composite bag; v) The bags from step iv were dried in a vacuum oven at 70°C; vi) The bag from step v was filled with an organic carbonate based electrolyte containing LiPF6; vii) the bag from step vi was sealed; viii) left to stand for 16 hours; ix) The cell was charged at a rate of C / 50 to 4.2V for 8 hours, then charged at a rate of 0.5C to 4.2V for 2 hours, then rested for 20 minutes, then discharged at a rate of 0.5C to 2.8V; x) The cells were punctured under vacuum to release the gases and then resealed. The fabricated cells were used for evaluation and other tests such as discharge capability test at 50°C, impact test, cycle life test etc.

[0161] Figure 20 shows the cell impedance at 1 kHz, the capacity at currents of 1 A, 3 A, 6 A, and 10 A, and the ratio of the capacity at 3, 6, and 10 A to the capacity at 1 A. Figure 22 shows the temperature profile of the cell during the shock test. Figure 23 shows the maximum cell temperature during the shock test. Figure 28 shows the maximum cell temperature during the 12 V / 2 A overcharge test.

[0162] Example 5 The preparation of the gas generating agent containing 52% CaCo3 and 48% PVDF, the resistance layer, the positive and negative electrodes, and the preparation of the completed cell No. 6 used for resistance measurement, discharge capacity test at 50°C, impact test, and cycle life evaluation are described below.

[0163] A) Positive electrode POS6B as an example of gas generating agent and resistance layer (first layer) preparation i) PVDF (23.25 g) was dissolved in NMP (~250 g); ii) The solution prepared in step i was mixed, then carbon black (1.85 g) was added and mixed at 6500 rpm for 10 minutes; iv) Nano CaCo3 powder (24.9 g) was added to the solution prepared in step iii and mixed at 6500 rpm for 20 minutes to make a flowable slurry; v) The slurry was coated onto 15 μm thick aluminum foil using an automated coater with a first heating zone set at about 135° C. and a second heating zone set at about 165° C., and the NMP was allowed to evaporate. The final solid loading was about 1 mg / cm. 2 It was.

[0164] B) Preparation of POS6A as an example of positive electrode preparation (second layer) i) PVDF (24 g) was dissolved in NMP (300 g); ii) Carbon black (12 g) was added and mixed at 6500 rpm for 15 minutes; iii) LiNi 0.4 Co 0.3 Mn 0.4 Co 0.3 O2(NMC) (558 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) some NMP was added to adjust the viscosity; v) The slurry was coated onto POS6B (Example 5A) using an automated coater with a first heating zone set at about 85° C. and a second heating zone set at about 135° C., and the NMP was allowed to evaporate. The final solids loading was about 22 mg / cm. 2 The positive electrode layer was then compressed to a thickness of about 167 μm. The fabricated electrode was used for impedance measurements at 0 V, which was taken as zero voltage against a standard graphite electrode, to examine the relationship with temperature.

[0165] C) Preparation of NEG6A as an example of negative electrode preparation i) CMC (9 g) was dissolved in deionized water (~530 g); ii) Carbon black (12 g) was added and mixed at 6500 rpm for 15 minutes; iii) Activated graphite for anode (JFE Chemical Corporation, graphitized mesophase carbon microbeads (MCMB)) (564 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (30 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 5 minutes; v) Some water was added to adjust the viscosity for smooth application; vi) Using an automated coater with a first heating zone set at about 95°C and a second heating zone set at about 125°C, the slurry was coated onto a 9 μm thick copper foil and the water was allowed to evaporate. The final solids loading was about 12 mg / cm. 2 The negative electrode layer was then compressed to a thickness of about 170 μm. The fabricated negative electrode was dried for cell assembly.

[0166] D) Preparation of cells for evaluation i) Electrodes were punched out to produce individual pieces having electrode tabs; ii) the positive electrode was dried at 125°C for 10 hours and the negative electrode was dried at 140°C for 10 hours; iii) A positive electrode and a negative electrode are laminated with a separator as an intermediate layer; iv) The jelly roll prepared in step iii was laid flat in an aluminum composite bag; v) The bags from step iv were dried in a vacuum oven at 70°C; vi) The bag from step v was filled with an organic carbonate based electrolyte containing LiPF6; vii) the bag from step vi was sealed; viii) left to stand for 16 hours; ix) The cell was charged at a rate of C / 50 to 4.2V for 8 hours, then charged at a rate of 0.5C to 4.2V for 2 hours, then rested for 20 minutes, then discharged at a rate of 0.5C to 2.8V; x) The cells were punctured under vacuum to release the gases and then resealed. The fabricated cells were used for evaluation and other tests such as discharge capability test at 50°C, impact test, cycle life test etc.

[0167] Figure 20 shows the cell impedance at 1 kHz, the capacity at currents of 1 A, 3 A, 6 A, and 10 A, and the ratio of the capacity at 3, 6, and 10 A to the capacity at 1 A. Figure 22 shows the temperature profile of the cell during the shock test. Figure 23 shows the maximum temperature of the cell during the shock test. Figure 28 shows the maximum temperature of the cell during the overcharge test.

[0168] Example 6 The preparation of a positive electrode for measuring the chemical decomposition voltage is described below.

[0169] POS7B was generated according to the following method: i) deionized water (~300 g) was mixed with Carbopol®-934 (19.64 g); ii) To the slurry prepared in step i, Super P® (160 mg) and LiOH (200 mg) were added and mixed at 5000 rpm for 30 minutes; iii) The slurry was adjusted by adding an appropriate amount of deionized water to form a coatable slurry; iv) The slurry was coated onto 15 μm aluminum foil using an automated coater with a first heating zone set at about 135° C. and a second heating zone set at about 165° C., and the NMP was allowed to evaporate. The final solid loading was about 0.7 mg / cm. 2 It was.

[0170] POS8B was generated according to the following method: i) Deionized water (~100 g) was mixed with AI-50 (19.85 g); ii) To the slurry prepared in step i, Super P® (160 mg) was added and mixed at 5000 rpm for 30 minutes; iii) The slurry was adjusted by adding an appropriate amount of deionized water to form a coatable slurry; iv) The slurry was coated onto 15 μm aluminum foil using an automated coater with a first heating zone set at about 135° C. and a second heating zone set at about 165° C., and the NMP was allowed to evaporate. The final solid loading was about 0.7 mg / cm. 2 It was.

[0171] POS9B was generated according to the following method: i) Deionized water (~322 g) was mixed with 19.85 g of CMC-DN-800H; ii) To the slurry prepared in step i, Super P® (160 mg) was added and mixed at 5000 rpm for 30 minutes; iii) The slurry was adjusted by adding an appropriate amount of deionized water to form a coatable slurry; iv) The slurry was coated onto 15 μm aluminum foil using an automated coater with a first heating zone set at about 135° C. and a second heating zone set at about 165° C., and the NMP was allowed to evaporate. The final solid loading was about 0.7 mg / cm. 2 It was.

[0172] POS13B was generated according to the following method: i) Torlon® 4000TF (400 mg) was dissolved in NMP (4 g); ii) PVDF-A (2.4 g) was dissolved in NMP (30 g); iii) The above two solutions were mixed and Super P® (160 mg) was added and mixed at 5000 rpm for 30 minutes; iv) The slurry was coated onto 15 μm aluminum foil using an automated coater with a first heating zone set at about 13° C. and a second heating zone set at about 16° C., and the NMP was allowed to evaporate. The final solid loading was about 0.7 mg / cm 2 It was.

[0173] Example 7 Electrochemical testing of the positive electrodes coated with the gas evolution layer is described below.

[0174] The decomposition voltages of all resistive layers were performed at room temperature by linear sweep voltammetry using a VMP2 multichannel potentiostat instrument, using a three-electrode configuration (resistive layer as working electrode, lithium metal as reference electrode and counter electrode). A 0.3 cm x 2.0 m piece of resistive layer was the working electrode, and a 0.3 cm x 2.0 m piece of lithium was the reference electrode and counter electrode. These electrodes were placed in a glass containing LiPF6 ethylene carbonate-based electrolyte (5 g). The sweep rate was 5 mV / s within the voltage range of 0-6 V. Figures 31 and 33 show the decomposition voltage profiles of these compounds. Figures 32 and 34 show the peak currents and peak voltages for each of the compounds tested.

[0175] Example 8 The preparation of the CaCO3-based gas generating agent, resistive layer, positive and negative electrodes, as well as the preparation of the completed cell No. 7 used for resistance measurement, discharge capacity test at 50°C, impact test, and cycle life evaluation are described below. The gas generating layer can be a resistive layer if the content of the conductive additive is in a certain range such that the resistivity of the gas generating layer is greater (at least 50%) than the resistivity of the energy layer or layers that provide the majority (>50%) of the battery's discharge energy. The content of the gas generating layer can be 2% to 99%.

[0176] A) Positive electrode POS71A as an example of gas generation layer (first layer) preparation i) Torlon® 4000TF (0.9 g) was dissolved in NMP (10 g); ii) PVDF (5.25 g) was dissolved in NMP (~68 g); iii) the solutions prepared in steps i and ii were mixed, then carbon black (1.8 g) was added and mixed at a speed of about 6500 rpm for 10 minutes; iv) Nano CaCo3 powder (7.11 g) and 134.94 g LiNi 0.33 Al 0.33 Co 0.33 O2 was added to the solution prepared in step iii and mixed at 6500 rpm for 20 minutes to create a flowable slurry; v) The slurry was coated onto 15 μm thick aluminum foil using an automated coater with a first heating zone set at about 90° C. and a second heating zone set at about 140° C., and the NMP was allowed to evaporate. The final solid loading was about 4 mg / cm. 2 It was.

[0177] B) Preparation of POS071B as an example of positive electrode preparation (second layer) i) PVDF (25.2 g) was dissolved in NMP (327 g); ii) Carbon black (21 g) was added and mixed at 6500 rpm for 15 minutes; iii) LiNi 0.82 Al 0.03 Co 0.15 O2(NCA) (649 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) some NMP was added to adjust the viscosity; v) Using an automated coater with a first heating zone set at about 85° C. and a second heating zone set at about 135° C., the slurry was spread onto the POS71A and the NMP was allowed to evaporate. The final solids loading was about 20.4 mg / cm. 2 The positive electrode layer was then compressed to a thickness of about 155 μm.

[0178] C) Preparation of NEG015B as an example of negative electrode preparation i) CMC (15 g) was dissolved in deionized water (~951 g); ii) Carbon black (15 g) was added and mixed at 6500 rpm for 15 minutes; iii) Activated graphite for anode (JFE Chemical Corporation, graphitized mesophase carbon microbeads (MCMB)) (945 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (50 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 5 minutes; v) Some water was added to adjust the viscosity for smooth application; vi) Using an automated coater with a first heating zone set at about 100°C and a second heating zone set at about 130°C, the slurry was coated onto a 9 μm thick copper foil and the water was allowed to evaporate. The final solid loading was about 11 mg / cm. 2 The negative electrode layer was then compressed to a thickness of about 155 μm. The fabricated negative electrode was dried for cell assembly.

[0179] D) Preparation of cells for evaluation i) Electrodes were punched out to produce individual pieces having electrode tabs; ii) the positive electrode was dried at ∼125°C for 10 h and the negative electrode was dried at ∼140°C for 10 h; iii) A positive electrode and a negative electrode are laminated with a separator as an intermediate layer; iv) The jelly roll prepared in step iii was laid flat in an aluminum composite bag; v) The bags from step iv were dried in a vacuum oven at 70°C; vi) The bag from step v was filled with a carbonate based electrolyte; vii) the bag from step vi was sealed; viii) left to stand for 16 hours; ix) The cells were charged at a rate of C / 50 to 4.2 V for 8 hours, then charged at a rate of 0.5 C to 4.2 V for 2 hours, then rested for 20 minutes, then discharged at a rate of 0.5 C to 2.8 V. The prepared cells were used for evaluation and other tests such as overcharge tests.

[0180] 35 shows the overcharge voltage, cell temperature, and oven chamber temperature during the overcharge test (2A and 12V). The maximum temperature of the cell during the overcharge test was about 83° C., and the cell passed the overcharge test. Examples of the present subject matter can include, but are not limited to, articles (e.g., devices, systems, etc.), methods of making or using, material compositions, etc. consistent with the description herein.

[0181] Example 9 The following describes the preparation of the Al2O3-based gas generating agent, the resistance layer, the positive electrode, and the negative electrode, as well as the preparation of the completed cell 3 used for resistance measurement, discharge capacity test at 50°C, impact test, and cycle life evaluation.

[0182] A) Positive electrode POS3B as an example of resistive layer (first layer) preparation i) Torlon® 4000TF (1 g) was dissolved in NMP (10 g); ii) PVDF (6 g) was dissolved in NMP (70 g); iii) the solutions prepared in steps i and ii were mixed, then carbon black (0.4 g) was added and mixed at a speed of about 6500 rpm for 10 minutes; iv) Nano Al2O3 powder (42 g) was added to the solution prepared in step iii and mixed at 6500 rpm for 20 minutes to make a flowable slurry; v) The slurry was coated onto 15 μm thick aluminum foil using an automated coater with a first heating zone set at about 130° C. and a second heating zone set at about 160° C., and the NMP was allowed to evaporate. The final solid loading was about 1 mg / cm. 2 It was.

[0183] B) Preparation of POS071B as an example of positive electrode preparation (second layer) i) PVDF (21.6 g) was dissolved in NMP (250 g); ii) Carbon black (18 g) was added and mixed at 6500 rpm for 15 minutes; iii) LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NMC) (560.4 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) some NMP was added to adjust the viscosity; v) Using an automated coater with a first heating zone set at about 85° C. and a second heating zone set at about 135° C., the slurry was spread onto POS3B and the NMP was allowed to evaporate. The final solids loading was about 19.4 mg / cm 2The positive electrode layer was then compressed to a thickness of about 153 μm. The fabricated electrode was used for impedance measurements at 0 V, which was taken as zero voltage against a standard graphite electrode, to examine the relationship with temperature.

[0184] C) Preparation of NEG3A as an example of negative electrode preparation i) CMC (13 g) was dissolved in deionized water (~1000 g); ii) Carbon black (20 g) was added and mixed at 6500 rpm for 15 minutes; iii) Activated graphite for the anode (JFE Chemical Corporation, graphitized mesophase carbon microbeads (MCMB) and synthetic graphite (TIMCAL)) (total 945.92 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (42 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 5 minutes; v) Some water was added to adjust the viscosity for smooth application; vi) The slurry was coated onto a 9 μm thick copper foil using an automated coater with a first heating zone set at about 100° C. and a second heating zone set at about 130° C., and the water was allowed to evaporate. The final solids loading was about 11.8 mg / cm. 2 The negative electrode layer was then compressed to a thickness of about 159 μm. The fabricated negative electrode was dried for cell assembly.

[0185] D) Preparation of cells for evaluation i) Electrodes were punched out to produce individual pieces having electrode tabs; ii) the positive electrode was dried at 125°C for 10 hours and the negative electrode was dried at 140°C for 10 hours; iii) A positive electrode and a negative electrode are laminated with a separator as an intermediate layer; iv) The jelly roll prepared in step iii was laid flat in an aluminum composite bag; v) The bags from step iv were dried in a vacuum oven at 70°C; vi) The bag from step v was filled with an organic carbonate based electrolyte containing LiPF6; vii) the bag from step vi was sealed; viii) left to stand for 16 hours; ix) The cells were charged at C / 50 rate to 4.2V for 8 hours, then charged at 0.5C rate to 4.2V for 2 hours, then rested for 20 minutes, then discharged at 0.5C rate to 2.8V. The cells were punctured under vacuum to release gases and then resealed. The fabricated cells were used for evaluation and other tests such as discharge capability test at 50°C, shock test, cycle life test, etc.

[0186] FIG. 38 shows the change in resistance with increasing temperature for the positive electrode recovered from the disassembled 4.09 V cell. The change in resistance is smaller than that of the reference cell (FIG. 37). FIG. 42 shows the relationship between the number of cycles and the discharge capacity. The cell lost about 2% capacity, which is similar to that of the reference cell (2.5%). FIG. 36 shows the cell impedance at 1 kHz, the capacity at currents of 1 A, 3 A, 6 A, and 10 A, and the ratio of the capacity at 3, 6, and 10 A to the capacity at 1 A. FIG. 40 shows the cell temperature profile during the shock test. FIG. 41 shows the maximum temperature of the cell during the shock test.

[0187] Example 10 The fabrication of the resistive layer, comprising 50% polyacrylic latex and 50% barium titanate (BaTiO2), the positive and negative electrodes, and the fabrication of the complete cell 4 used for resistance measurements, discharge capability testing at 50°C, impact testing, and cycle life evaluation are described below.

[0188] A) Positive electrode POS4B as an example of resistive layer (first layer) preparation i) CMC (0.375 g) was dissolved in deionized water (~30 g); ii) The solution prepared in step i was mixed, then carbon black (1.75 g) was added and mixed for a few minutes; iii) Nano BaTiO2 powder (25 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 20 minutes to make a flowable slurry; v) The slurry was coated onto 15 μm thick aluminum foil using an automated coater with a first heating zone set at about 90° C. and a second heating zone set at about 140° C., and the water was allowed to evaporate. The final solid loading was about 0.7 mg / cm. 2 It was.

[0189] B) Preparation of POS4A as an example of positive electrode preparation (second layer) i) PVDF (14.4 g) was dissolved in NMP (~160 g); ii) Carbon black (12 g) was added and mixed at 6500 rpm for 15 minutes; iii) LiNi 0.5 Mn 0.3 Co 0.2 O2(NMC) (373.6 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) some NMP was added to adjust the viscosity; v) The slurry was coated onto POS4B (Example 2A) using an automated coater with a first heating zone set at about 80° C. and a second heating zone set at about 130° C., and the NMP was allowed to evaporate. The final solids loading was about 15.2 mg / cm. 2 The positive electrode layer was then compressed to a thickness of about 113 μm. The fabricated electrode was used for impedance measurements at 0 V, which was taken as zero voltage against a standard graphite electrode, to examine the relationship with temperature.

[0190] C) Preparation of NEG3A as an example of negative electrode preparation i) CMC (7.8 g) was dissolved in deionized water (~800 g); ii) Carbon black (12 g) was added and mixed at 6500 rpm for 15 minutes; iii) Activated graphite for the anode (JFE Chemical Corporation, graphitized mesophase carbon microbeads (MCMB) and synthetic graphite (TIMCAL)) (568.6 g in total) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (25.2 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 5 minutes; v) Some water was added to adjust the viscosity for smooth application; vi) The slurry was coated onto a 9 μm thick copper foil using an automated coater with a first heating zone set at about 70° C. and a second heating zone set at about 100° C., and the water was allowed to evaporate. The final solids loading was about 8.99 mg / cm. 2 The negative electrode layer was then compressed to a thickness of about 123 μm. The fabricated negative electrode was dried for cell assembly.

[0191] D) Preparation of cells for evaluation i) Electrodes were punched out to produce individual pieces having electrode tabs; ii) the positive electrode was dried at 125°C for 10 hours and the negative electrode was dried at 140°C for 10 hours; iii) A positive electrode and a negative electrode are laminated with a separator as an intermediate layer; iv) The jelly roll prepared in step iii was laid flat in an aluminum composite bag; v) The bags from step iv were dried in a vacuum oven at 70°C; vi) The bag from step v was filled with an organic carbonate based electrolyte containing LiPF6; vii) the bag from step vi was sealed; viii) left to stand for 16 hours; ix) The cells were charged at C / 50 rate to 4.2V for 8 hours, then charged at 0.5C rate to 4.2V for 2 hours, then rested for 20 minutes, then discharged at 0.5C rate to 2.8V. The cells were punctured under vacuum to release gases and then resealed. The fabricated cells were used for evaluation and other tests such as discharge capability test at 50°C, shock test, cycle life test, etc.

[0192] Figure 39 shows the discharge capacity at 50°C at currents of 1A, 3A and 6A. The cell capacity decreases rapidly with increasing current, indicating the strong influence of the resistive layer. Figure 36 shows the cell impedance at 1 kHz, the capacity at currents of 1A, 3A, 6A and 10A, and the ratio of the capacity at 3, 6 and 10A to the capacity at 1A. Figure 40 shows the cell temperature profile during the shock test. Figure 41 shows the maximum cell temperature during the shock test.

[0193] Example 11 The preparation of the resistive layer in the negative electrode, the positive electrode, and the negative electrode, as well as the preparation of a completed cell 5 for use in resistance measurements, discharge capacity testing at 50° C., impact testing, and cycle life evaluation, are described below.

[0194] A) Preparation of POS5A as an example of positive electrode preparation i) PVDF (31.5 g) was dissolved in NMP (~340 g); ii) Carbon black (13.5 g) was added and mixed at 6500 rpm for 15 minutes; iii) LiNi 0.33 Mn 0.33 Co 0.33 O2(NMC) (855 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) some NMP was added to adjust the viscosity; v) The slurry was coated onto 15 μm aluminum foil using an automated coater with a first heating zone set at about 80° C. and a second heating zone set at about 130° C., and the NMP was allowed to evaporate. The final solid loading was about 14.8 mg / cm. 2 The cathode layer was then compressed to a thickness of about 113 μm. The fabricated electrode was used for impedance measurements at 0 V, taken as zero voltage against a standard graphite electrode, to study the relationship with temperature, and then dried for cell assembly.

[0195] B) Preparation of NEG5B as an example of negative electrode preparation (first layer) i) CMC (0.375 g) was dissolved in deionized water (~90 g); ii) Carbon black (1.75 g) was added and mixed at 6500 rpm for 15 minutes; iii) BaTiO2 (total of 25 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (45.6 g) was added to the slurry prepared in step iii and mixed at 6500 rpm for 5 minutes; v) Viscosity adjusted for smooth application; vi) The slurry was coated onto a 9 μm thick copper foil using an automated coater equipped with a first heating zone set at approximately 90° C. and a second heating zone set at approximately 140° C., and the water was allowed to evaporate.

[0196] C) Preparation of NEG5A as an example of negative electrode preparation (second layer) i) CMC (3.9 g) was dissolved in deionized water (~350 g); ii) Carbon black (6 g) was added and mixed at 6500 rpm for 15 minutes; iii) Activated graphite for the anode (JFE Chemical Corporation, graphitized mesophase carbon microbeads (MCMB) and synthetic graphite (TIMCAL)) (total 283.8 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (25.2 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 5 minutes; v) Viscosity adjusted for smooth application; vi) Using an automated coater with a first heating zone set at about 70°C and a second heating zone set at about 100°C, the slurry was coated onto NEG5B and the water was allowed to evaporate. The final solids loading was about 9.8 mg / cm 2 The negative electrode layer was then compressed to a thickness of about 114 μm. The fabricated negative electrode was dried for cell assembly.

[0197] D) Preparation of cells for evaluation i) Electrodes were punched out to produce individual pieces having electrode tabs; ii) the positive electrode was dried at 125°C for 10 hours and the negative electrode was dried at 140°C for 10 hours; iii) A positive electrode and a negative electrode are laminated with a separator as an intermediate layer; iv) The jelly roll prepared in step iii was laid flat in an aluminum composite bag; v) The bags from step iv were dried in a vacuum oven at 70°C; vi) The bag from step v was filled with an organic carbonate based electrolyte containing LiPF6; vii) the bag from step vi was sealed; viii) left to stand for 16 hours; ix) The cells were charged at C / 20 rate to 4.2V for 5 hours, then charged at 0.5C rate to 4.2V for 2 hours, then rested for 20 minutes, then discharged at 0.5C rate to 2.8V. The cells were punctured under vacuum to release gases and then resealed. The fabricated cells were used for evaluation and other tests such as discharge capability test at 50°C, shock test, cycle life test, etc.

[0198] Figure 36 shows the cell impedance at 1 kHz, the capacity at currents of 1 A, 3 A, 6 A, and 10 A, and the ratio of the capacity at 3, 6, and 10 A to the capacity at 1 A. Figure 40 shows the cell temperature profile during the shock test. Figure 41 shows the maximum cell temperature during the shock test.

[0199] Example 12 The following describes the preparation of the resistive layer, positive and negative electrodes made of a mixture of Al2O3 and sodium silicate (NaSiO3), as well as the preparation of a completed cell 6 used for resistance measurement, discharge capacity testing at 50°C, impact testing, and cycle life evaluation.

[0200] A) Positive electrode POS6B as an example of resistive layer (first layer) preparation i) Torlon® 4000TF (0.8 g) was dissolved in NMP (~10 g); ii) PVDF (4.8 g) was dissolved in NMP (60 g); iii) the solutions prepared in steps i and ii were mixed, then carbon black (0.32 g) was added and mixed at a speed of about 6500 rpm for 10 minutes; iv) Nano Al2O3 powder (17.04 g) and NaSiO3 (17.04 g) were added to the solution prepared in step iii and mixed at 6500 rpm for 20 minutes to make a flowable slurry; v) The slurry was coated onto 15 μm thick aluminum foil using an automated coater with a first heating zone set at about 135° C. and a second heating zone set at about 165° C., and the NMP was allowed to evaporate. The final solid loading was about 0.7 mg / cm. 2 It was.

[0201] B) Preparation of POS6A as an example of positive electrode preparation (second layer) i) PVDF (21.6 g) was dissolved in NMP (270 g); ii) Carbon black (18 g) was added and mixed at 6500 rpm for 15 minutes; iii) LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NMC) (560.4 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) some NMP was added to adjust the viscosity; v) The slurry was coated onto POS6B (Example 1A) using an automated coater with a first heating zone set at about 85° C. and a second heating zone set at about 135° C., and the NMP was allowed to evaporate. The final solids loading was about 19.4 mg / cm 2 The positive electrode layer was then compressed to a thickness of about 153 μm. The fabricated electrode was used for impedance measurements at 0 V, which was taken as zero voltage against a standard graphite electrode, to examine the relationship with temperature.

[0202] C) Preparation of NEG6A as an example of negative electrode preparation i) CMC (13 g) was dissolved in deionized water (~1000 g); ii) Carbon black (20 g) was added and mixed at 6500 rpm for 15 minutes; iii) Activated graphite for the anode (JFE Chemical Corporation, graphitized mesophase carbon microbeads (MCMB) and synthetic graphite (TIMCAL)) (total 945.92 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 30 minutes to produce a flowable slurry; iv) SBR (50% solids, water suspension) (42 g) was added to the slurry prepared in step ii and mixed at 6500 rpm for 5 minutes; v) Viscosity adjusted for smooth application; vi) The slurry was coated onto a 9 μm thick copper foil using an automated coater with a first heating zone set at about 100° C. and a second heating zone set at about 130° C., and the water was allowed to evaporate. The final solids loading was about 11.8 mg / cm. 2 The negative electrode layer was then compressed to a thickness of about 159 μm. The fabricated negative electrode was dried for cell assembly.

[0203] D) Preparation of cells for evaluation i) Electrodes were punched out to produce individual pieces having electrode tabs; ii) the positive electrode was dried at 125°C for 10 hours and the negative electrode was dried at 140°C for 10 hours; iii) A positive electrode and a negative electrode are laminated with a separator as an intermediate layer; iv) The jelly roll prepared in step iii was laid flat in an aluminum composite bag; v) The bags from step iv were dried in a vacuum oven at 70°C; vi) The bag from step v was filled with an organic carbonate based electrolyte containing LiPF6; vii) the bag from step vi was sealed; viii) left to stand for 16 hours; ix) The cells were charged at C / 20 rate to 4.2V for 8 hours, then charged at 0.5C rate to 4.2V for 2 hours, then rested for 20 minutes, then discharged at 0.5C rate to 2.8V. The cells were punctured under vacuum to release gases and then resealed. The fabricated cells were used for evaluation and other tests such as discharge capability test at 50°C, shock test, cycle life test, etc.

[0204] Figure 36 shows the cell impedance at 1 kHz, the capacity at currents of 1 A, 3 A, 6 A, and 10 A, and the ratio of the capacity at 3, 6, and 10 A to the capacity at 1 A. Figure 40 shows the cell temperature profile during the shock test. Figure 41 shows the maximum cell temperature during the shock test.

[0205] In the above description and in the claims, phrases such as "at least one" or "one or more" may be followed by a conjunctive description of elements or features. The term "and / or" may appear in the description of more than one element or feature. Unless otherwise implicitly or explicitly contradicted by the context in which it is used, such phrases are intended to mean the described elements or features individually or in combination with any of the other described elements or features. For example, the phrases "at least one of A and B," "one or more of A and B," and "A and / or B" are intended to mean "A only, B only, or both A and B," respectively. A similar interpretation is intended to be given to descriptions containing more than two items. For example, the phrases "at least one of A, B, and C" and "A, B, and / or C" are intended to mean "A only, B only, C only, both A and B, both A and C, both B and C, or all of A, B, and C," respectively. Use of the term "based on" in the above description and claims is intended to mean "based at least in part on," allowing for unrecited features or elements.

[0206] The subject matter described herein may be embodied in systems, devices, methods, and / or articles, depending on the desired configuration. The embodiments described in the above description do not represent all embodiments consistent with the subject matter described herein. Rather, they are merely some examples consistent with aspects related to the described subject matter. Although a few variations have been described in detail in the above description, other modifications or additions are possible. In particular, further features and / or variations may be provided in addition to those described herein. For example, the above-described embodiments may be directed to various combinations and subcombinations of the disclosed features, and / or combinations and subcombinations of multiple additional features disclosed. In addition, the logic flow depicted in the accompanying drawings and described herein does not necessarily require the particular order or sequence depicted to achieve desired results. Other embodiments are within the scope of the following claims.

Claims

1. 1. An improved high energy density rechargeable battery comprising: A first electrode, a first current collector for conducting electrons; a current interrupter interposed between the first electrode and the first current collector, the current interrupter including a heat sensitive material configured to be activated by at least a temperature trigger to generate a gas, the generation of the gas forming a non-conductive gap between the first electrode and the first current collector, the formation of the non-conductive gap electrically isolating the first electrode and the first current collector; a second electrode having an opposite polarity to the first electrode; and a separator interposed between the first electrode and the second electrode.

2. 10. The battery of claim 1 further comprising a current limiter.

3. 3. The battery of claim 2 further comprising a second current collector.

4. 4. The battery of claim 3, wherein the current limiter is interposed between the second electrode and the second current collector.

5. 3. The battery of claim 2, wherein the current limiter is interposed between the first electrode and the first current collector.

6. 6. The battery of claim 5, wherein said current limiter and said current interrupter are incorporated together in a single protective layer interposed between said first electrode and said first current collector.

7. 7. The battery of claim 6, wherein the resistivity of the current limiter is greater than the internal resistivity of the first electrode at temperatures above a temperature range for normal operation.

8. 7. The battery of claim 6, wherein the resistivity of the current limiter does not shift with temperature within a temperature range for normal operation.

9. 7. The battery of claim 6, wherein the resistivity of the current limiter is less than the internal resistivity of the first electrode at a temperature within a temperature range for normal operation.

10. The battery of claim 1 , wherein the temperature trigger activates when the temperature exceeds a temperature range for normal operation.

11. 10. The battery of claim 1, wherein the heat sensitive material is further configured to be activated to generate the gas by a voltage trigger, the voltage trigger activating when a voltage exceeds a voltage range for normal operation.

12. 2. The battery of claim 1, wherein said first electrode and said first current collector are electrically coupled when said current interrupter is in a disengaged configuration, and said non-conductive gap is formed between said first electrode and said first current collector when said current interrupter is in an engaged configuration.

13. The battery of claim 12 , wherein the thermally sensitive material is configured to transition from the disengaged configuration to the engaged configuration upon activation of at least the temperature trigger.

14. 13. The battery of claim 12, wherein a lamination connection provided by the current interrupter electrically connects the first electrode and the first current collector when the current interrupter is in a disengaged configuration, and the formation of the non-conductive gap releases the lamination connection between the first electrode and the first current collector.

15. forming a non-conductive gap between an electrode and a current collector within the battery; the non-conductive gap is formed by a heat sensitive material adapted to be activated by at least a temperature trigger to generate a gas, the heat sensitive material including a barrier layer interposed between the electrode and the current collector, and formation of the non-conductive gap electrically isolates the electrode from the current collector.

Citation Information

Patent Citations

  • Positive temperature coefficient (PTC) material used for heat safety protection of lithium ion battery, and application thereof

    CN103194161A

  • Nonaqueous electrolyte secondary battery

    JP2005011540A

  • Conductive composition

    JP2010146726A

  • Battery

    JP2012074359A